Method for producing nanocrystalline films

The method of light-irradiating a metal member in water to form nanocrystalline films addresses the limitations of existing patterning techniques by providing a precise, cost-effective, and environmentally friendly process for creating metal oxide thin films with desired patterns on diverse substrates.

JP7607293B2Active Publication Date: 2024-12-27RESONAC CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023074781
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-02-01
Filing Date
2023-04-28
Publication Date
2024-12-27
Estimated Expiration
2039-02-01

AI Technical Summary

Technical Problem

Existing methods for patterning metal oxide thin films are complex, hazardous, costly, and limited in pattern precision and substrate compatibility, often requiring high-temperature processes and harsh chemical solutions, which can degrade film quality and introduce impurities.

Method used

A method involving light irradiation of a metal member immersed in water to form a nanocrystalline film with a desired pattern, utilizing the difference in standard electrode potentials of metals to selectively generate nanocrystals on the surface, avoiding high-temperature and vacuum processes.

Benefits of technology

Enables the easy formation of nanocrystalline films with precise patterns on various substrates at ambient conditions, reducing environmental impact and process costs while maintaining film quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607293000011
    Figure 0007607293000011
  • Figure 0007607293000012
    Figure 0007607293000012
  • Figure 0007607293000013
    Figure 0007607293000013
Patent Text Reader

Abstract

To provide a method for manufacturing a nano crystal film having a desired pattern.SOLUTION: A method for manufacturing a nano crystal film comprises a light irradiation step of irradiating the surface of a metal member (150) in water with light to form a nano crystal film (25) having a predetermined pattern on the surface of the metal member. A nano crystal in the nano crystal film includes at least one kind of oxide and hydroxide. The metal member includes: a first member (22d) including first metal and a mask material (36) overlapping with the surface of the first member and fixed to the surface of the first member. The water intervenes between the first member and the mask material. The normal electrode potential of the first metal is higher than -2.00 V. An exposed portion (90) without overlapping with the mask material on the surface of the first member has a predetermined pattern along the surface of the first member. In the light irradiation step, the nano crystal film is formed on the surface of the exposed portion. The oxide is the oxide of the first metal, and the hydroxide is the hydroxide of the first metal.SELECTED DRAWING: Figure 10
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing nanocrystalline films. [Background technology]

[0002] Metal oxide thin films are currently attracting attention, and are widely used industrially as semiconductors, insulators, superconductors, transparent conductive films, piezoelectrics, photocatalysts, protective films, etc., depending on the various physical properties of metal oxides. In particular, in recent years, research on optical devices and electronic devices focusing on the semiconductor properties of metal oxide thin films has been actively conducted. For example, the application of metal oxide thin films to thin film transistors, light-emitting diodes, various sensors, etc. is being promoted. Metal oxides that exhibit semiconductor properties include oxides or composite oxides such as zinc oxide (ZnO), copper oxide (CuO and Cu2O), titanium oxide (TiO2), nickel oxide (NiO), cadmium oxide (CdO), gallium oxide (Ga2O3), indium oxide (In2O3), tin oxide (SnO2), copper aluminum oxide (CuAlO2), and indium-gallium-zinc oxide (In-Ga-Zn-O:IGZO).

[0003] Metal oxides with a band gap large enough to transmit visible light are suitable for transparent conductive films. Examples of such metal oxides include tin-doped indium oxide (In2O3:Sn, ITO), fluorine-doped tin oxide (SnO2:F, FTO), and aluminum-doped zinc oxide (ZnO:Al). Tungsten oxide (WO3) and niobium oxyfluoride (NbO2F) are also known as electrochromic materials whose optical properties change when an electric field or current is applied. Research is also being conducted on the application of thin films of these electrochromic materials to optical devices.

[0004] The metal oxide thin film is generally produced by sputtering, vacuum deposition, ion plating, laser ablation, sol-gel, hydrothermal synthesis, coprecipitation, and chemical vapor deposition. Also known is a film-forming method in which a precursor of a metal oxide (oxide semiconductor) is applied to a substrate surface by dipping, screen printing, spin coating, spraying, or the like, and the coating of the precursor is oxidized by heating or the like.

[0005] On the other hand, it is known that nanocrystals made of metal oxides exhibit different physical and chemical properties (melting / sintering temperature, luminescence / fluorescence properties, photocatalytic activity, etc.) from the bulk as their size decreases, and research into the deposition technologies for metal oxide thin films made of these nanocrystals is also being actively conducted.

[0006] In order to widely use metal oxide thin films industrially, a technology for forming metal oxide thin films only at desired locations on the surface of a substrate (so-called patterning) is required. In particular, precise wiring and arrangement of metal oxide thin films are required for liquid crystal displays and circuit boards, and control of the deposition position is required for semiconductor devices such as thin film transistors.

[0007] As a method for patterning a metal oxide thin film, the following Patent Documents 1 to 4 disclose a method in which a metal oxide thin film is formed on the entire surface of a substrate by sputtering, vacuum deposition, or the like, and then the metal oxide thin film is patterned by photolithography. In this patterning method, a photosensitive material (photoresist) is applied to the surface of the metal oxide thin film, the metal oxide thin film is exposed to light such as ultraviolet light using a pattern mask, and the exposed and unexposed areas are removed by development and etching, and the remaining photoresist is peeled off.

[0008] Patent Document 5 discloses a method in which an ink consisting of a metal oxide precursor is directly applied onto a substrate by screen printing or the like, the ink is patterned, and then a metal oxide thin film is formed by a heat treatment. Specifically, an amine having a hydroxyl group or an oxygen-containing heterocyclic amine is added to an organic solvent to induce hydrogen bonding between molecules, thereby improving the viscosity of the ink precursor.

[0009] Non-Patent Document 1 discloses a method for directly forming a pattern consisting of zinc oxide nanoparticles using an aqueous solution method. This patterning method includes a step of immersing a substrate in a phenyltrichlorosilane solution to form an organic thin film layer, a step of exposing a part of the organic thin film layer with a mask pattern to modify it, a step of immersing the organic thin film layer in a palladium (Pd) catalyst solution to support the Pd catalyst on the unmodified part of the organic thin film layer, and a step of immersing the organic thin film layer in a neutral reaction aqueous solution in which zinc is dissolved, and selectively promotes the precipitation reaction of zinc oxide (ZnO) only in the catalyst-supported part.

[0010] Non-Patent Document 2 discloses a method for directly forming zinc oxide (ZnO) nanorods using the principle of a galvanic cell without the need for a seed layer. Specifically, a base metal film such as aluminum is formed on a substrate, and a precious metal film such as platinum (Pt) or copper (Cu) is formed in an arbitrary pattern on the non-metal film. Next, the substrate is heated in an aqueous solution containing zinc nitrate or the like. At this time, Al of the base metal film becomes the anode and dissolves into the aqueous solution, flowing onto the surface of the precious metal film (cathode), whereby a hydrothermal synthesis reaction proceeds on the precious metal film side, and finally, zinc oxide (ZnO) nanorods are selectively precipitated on the surface of the precious metal film. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] JP 2007-227300 A [Patent Document 2] JP 2006-196201 A [Patent Document 3] JP 2011-134495 A [Patent Document 4] Japanese Patent Application Publication No. 7-304998 [Patent Document 5] JP 2014-143403 A [Non-patent literature]

[0012] [Non-Patent Document 1] N. Saito et al., “Characterization of ZincOxide Micropatterns Deposited onSelf-Assembled Monolayer Template”, J. Ceram.Soc. Jpn, vol. 110, no. 5, pp. 386-390, 2002. [Non-Patent Document 2] Z. Zheng et al., “General Route to ZnONanorod Arrays on Conducting Substrates via Galvanic-cell-based approach”, ScientificReports 3:2434, DOI: 10. 1038, 2013. Summary of the Invention [Problem to be solved by the invention]

[0013] In the patterning of metal oxide thin films by photolithography, fine patterns of the order of 1 μm can be formed, but the process required for patterning is long and complicated. In addition, in the methods described in Patent Documents 1 to 3, the developing solution, etching solution, and stripping solution used in photolithography are strongly acidic or strongly alkaline, so that patterning is dangerous and waste liquid is costly. Furthermore, among metal oxides, amphoteric oxides such as zinc oxide may dissolve during the etching process.

[0014] In the method described in Patent Document 4, a process of washing the metal oxide thin film with water is carried out after exposure, and the parts not irradiated with ultraviolet light are dissolved and removed with water, so that only the parts of the metal oxide thin film that were irradiated with ultraviolet light remain on the surface of the substrate. In the case of this method, the process up to exposure is generally the same as the methods described in Patent Documents 1 to 3, and problems such as complicated processes and high costs remain.

[0015] The method described in Patent Document 5 does not require a vacuum process such as a sputtering method or a vacuum deposition method, or an etching process, and is considered to be applicable to large-area patterning of metal oxide thin films. However, the method described in Patent Document 5 requires a heat treatment at high temperature to remove organic solvents, and therefore the substrate on which the metal oxide precursor is printed is limited to heat-resistant glass, etc. In addition, it is difficult to form a pattern with dimensions of 10 μm or less by screen printing of the precursor.

[0016] Furthermore, since the metal oxide thin films formed by the processes described in Patent Documents 1-5 have a constant and uniform thickness, films containing metal oxide nanocrystals cannot be formed by the methods described in Patent Documents 1-5.

[0017] The method of Non-Patent Document 1 does not require heat treatment or etching, so there are more options for substrates and it is easy to control the shape of the metal oxide thin film. However, the method of Non-Patent Document 1 requires a separate exposure device such as a photolithography device, so the process cost is high and it is difficult to pattern a large-area metal oxide thin film.

[0018] In the method of Non-Patent Document 2, the growth of zinc oxide (ZnO) does not depend on the type of substrate, so that a conductive substrate such as ITO or FTO can be used. However, the hydrothermal synthesis reaction generally requires a strongly acidic or strongly alkaline reaction solution and is accompanied by a high-temperature process, which places a large burden on the environment. In addition, the metal oxide thin film obtained by the hydrothermal synthesis reaction is likely to contain impurities, so that the properties of the metal oxide thin film as a metal oxide may be deteriorated when the metal oxide thin film is applied to the above-mentioned devices.

[0019] The present invention has been made in consideration of the above circumstances, and aims to provide a method for manufacturing a nanocrystalline film that contains at least one of a metal oxide and a metal hydroxide and can easily form a nanocrystalline film having a desired pattern. [Means for solving the problem]

[0020] A method for producing a nanocrystalline film according to one aspect of the present invention includes a light irradiation step of forming a nanocrystalline film having a predetermined pattern on the surface of a metal member immersed in water by irradiating the surface of the metal member with light, and the nanocrystals contained in the nanocrystalline film include at least one of an oxide and a hydroxide, the oxide being an oxide of a metal derived from the metal member, and the hydroxide being a hydroxide of a metal derived from the metal member.

[0021] The metal member may have a first member containing a first metal and a second member containing a second metal, the standard electrode potential of the first metal may be higher than -2.00V, the standard electrode potential of the second metal may be higher than -2.00V, the standard electrode potential of the first metal may be lower than the standard electrode potential of the second metal, the difference between the standard electrode potentials of the first metal and the second metal may be greater than 0.20V, the first member and the second member may be electrically connected, the second member may be disposed on a surface of the first member, the second member may have a predetermined pattern along the surface of the first member, in the light irradiation step, the nanocrystal film may be formed on the surface of the second member, the oxide contained in the nanocrystals may be an oxide of the first metal, and the hydroxide contained in the nanocrystals may be a hydroxide of the first metal.

[0022] The metal member may have a first member containing a first metal, the standard electrode potential of the first metal may be higher than -2.00 V, the first member may be a pattern structure having a predetermined pattern, in the light irradiation step, a nanocrystal film may be formed on the surface of the first member, the oxide contained in the nanocrystals may be an oxide of the first metal, and the hydroxide contained in the nanocrystals may be a hydroxide of the first metal.

[0023] The metal member may have a first member containing a first metal, a substrate, and a conductive film disposed on the surface of the substrate, the standard electrode potential of the first metal may be higher than -2.00 V, the first member and the conductive film may be electrically connected, the conductive film may have a predetermined pattern along the surface of the substrate, in the light irradiation step, a nanocrystal film may be formed on the surface of the conductive film, the oxide contained in the nanocrystals may be an oxide of the first metal, and the hydroxide contained in the nanocrystals may be a hydroxide of the first metal.

[0024] The metal member may have a first member containing a first metal and a mask material overlapping a surface of the first member, water may be interposed between the first member and the mask material, the standard electrode potential of the first metal may be higher than -2.00V, an exposed portion of the surface of the first member that does not overlap with the mask material may have a predetermined pattern along the surface of the first member, and in the light irradiation process, a nanocrystal film may be formed on the surface of the exposed portion, the oxide contained in the nanocrystals may be an oxide of the first metal, and the hydroxide contained in the nanocrystals may be a hydroxide of the first metal.

[0025] The metallic member may include an alloy.

[0026] The content of the first metal in the first member may be 10.0 to 100.0 mass % based on the total mass of the first member, and the content of the second metal in the second member may be 10.0 to 100.0 mass % based on the total mass of the second member.

[0027] The pattern structure may have at least one of a mesh structure and a lattice structure.

[0028] The substrate may be at least one selected from the group consisting of glass, ceramics, metals covered with insulating material, semiconductors covered with insulating material, and plastics.

[0029] The conductive film may contain at least one selected from the group consisting of copper, silver, gold, platinum, aluminum, chromium, nickel, iron, tin, lead, indium tin oxide (ITO), fluorine-doped tin oxide (FTO), and aluminum-doped zinc oxide.

[0030] The first member and the conductive film may be connected by a wiring material containing at least one selected from the group consisting of copper, silver, gold, platinum, aluminum, chromium, nickel, iron, tin, and lead.

[0031] The conductive film may include a second metal, the standard electrode potential of the second metal may be greater than −2.00 V, the standard electrode potential of the first metal may be less than the standard electrode potential of the second metal, and the difference between the standard electrode potentials of the first and second metals may be greater than 0.20 V.

[0032] The area of ​​the exposed portion may be represented as S1, the area of ​​the overlapping portion of the surface of the first member where the mask material overlaps may be represented as S2, and the area ratio S2 / S1 may be 1 / 200 to 1 / 2.

[0033] The light may be sunlight or simulated sunlight.

[0034] In the spectrum of light, the wavelength at which the intensity is maximum may be greater than or equal to 360 nm and less than 620 nm.

[0035] The water may be at least one type selected from the group consisting of pure water, ion-exchanged water, rainwater, tap water, river water, well water, filtered water, distilled water, reverse osmosis water, spring water, spring water, dam water, and seawater.

[0036] The pH of the water may be from 5.00 to 10.0.

[0037] The electrical conductivity of the water may be 0.05 to 1.0 μS / cm.

[0038] The nanocrystal may have at least one shape selected from the group consisting of needle-like, column-like, rod-like, tubular, scale-like, lump-like, flower-like, starfish-like, branch-like and convex-like shapes.

[0039] The first metal may be at least one selected from the group consisting of aluminum, titanium, manganese, vanadium, zinc, iron, nickel, tin, lead, and copper.

[0040] The method for producing a nanocrystal film according to one aspect of the present invention may further include a film formation step of forming an oxide semiconductor layer on the surface of the metal member prior to the light irradiation step. Effect of the Invention

[0041] According to the present invention, there is provided a method for producing a nanocrystal film, which can easily form a nanocrystal film containing at least one of a metal oxide and a metal hydroxide and having a desired pattern. [Brief description of the drawings]

[0042] [Figure 1] FIG. 1 is a schematic diagram (perspective view) showing a method for producing a nanocrystal film according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram (perspective view) showing a method for producing a nanocrystal film according to one embodiment of the present invention. [Diagram 3] (a) in Figure 3 is a schematic diagram (oblique view) of a metal component according to the first embodiment of the present invention, and (b) in Figure 3 is a schematic diagram of a cross section (cross section perpendicular to the surface of the metal component) of the metal component shown in (a) in Figure 3 and a cross section of a nanocrystalline film formed on the surface of the metal component. [Figure 4] FIG. 4 is a schematic diagram of a metal member (pattern structure) according to a second embodiment of the present invention. [Diagram 5](a) in Figure 5 is a schematic diagram of an example of a pattern of a metal member (pattern structure) according to the second embodiment, (b) in Figure 5 is a schematic diagram of an example of a pattern of a metal member (pattern structure) according to the second embodiment, and (c) in Figure 5 is a schematic diagram of an example of a pattern of a metal member (pattern structure) according to the second embodiment. [Figure 6] FIG. 6 is a schematic view (perspective view) of a metal member according to a third embodiment of the present invention. [Figure 7] FIG. 7 is a schematic view (perspective view) of a metal member according to a third embodiment of the present invention. [Figure 8] FIG. 8 is a schematic diagram (top view) of a base material and a conductive film of a metal member according to a third embodiment of the present invention. [Figure 9] (a) in Figure 9 is a schematic diagram (oblique view) of a metal member according to the fourth embodiment of the present invention, (b) in Figure 9 is a schematic diagram of a cross section (cross section perpendicular to the surface of the metal member) of the metal member shown in (a) in Figure 9, and (c) in Figure 9 is a schematic diagram of the cross section (cross section perpendicular to the surface of the metal member) of the metal member shown in (a) in Figure 9 and a cross section of a nanocrystalline film formed on the surface of the metal member. [Figure 10] (a) in Figure 10 is a schematic diagram (oblique view) of a metal member according to the fourth embodiment of the present invention, (b) in Figure 10 is a schematic diagram of a cross section (cross section perpendicular to the surface of the metal member) of the metal member shown in (a) in Figure 10, and (c) in Figure 10 is a schematic diagram of the cross section (cross section perpendicular to the surface of the metal member) of the metal member shown in (a) in Figure 10 and a cross section of a nanocrystalline film formed on the surface of the metal member. [Figure 11] FIG. 11 is an image taken with a scanning electron microscope (SEM) showing rod-shaped nanocrystals according to an embodiment of the present invention. [Figure 12] FIG. 12 is an image taken with a scanning electron microscope (SEM) showing flower-shaped nanocrystals according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0043] A preferred embodiment of the present invention will be described in detail below. However, the present invention is not limited to the following embodiment. Not only an independent process, but also a process that cannot be clearly distinguished from other processes is implied in the term "process" as long as its purpose is achieved. A numerical range indicated using "~" includes the numerical values ​​written before and after "~" as the minimum and maximum values, respectively. When multiple substances corresponding to each component are present in the composition, the content of each component in the composition means the total content of the multiple substances present in the composition, unless otherwise specified. In the drawings, equivalent components are given the same symbols.

[0044] [Outline of nanocrystalline film manufacturing method] The method for producing a nanocrystalline film according to the present invention includes a light irradiation step. For example, as shown in FIG. 1, in the light irradiation step, a surface of a metal member 100 immersed in water 2 is irradiated with light L to form a nanocrystalline film having a predetermined pattern on the surface of the metal member 100. The predetermined pattern means a shape that is designed and determined in advance before forming the nanocrystalline film. The nanocrystalline film may be an aggregate of a plurality (a large number) of nanocrystals. The nanocrystalline film may be a polycrystal containing a plurality (a large number) of nanocrystals. The nanocrystalline film may be composed only of nanocrystals. The nanocrystals contained in the nanocrystalline film include at least one of an oxide and a hydroxide, the oxide being an oxide of a metal derived from the metal member 100, and the hydroxide being a hydroxide of a metal derived from the metal member 100. The method for producing a nanocrystalline film according to the present invention may be rephrased as a method for patterning a nanocrystalline film. The method for producing a nanocrystalline film according to the present invention may further include a film formation step of forming an oxide semiconductor layer on the surface of the metal member before the light irradiation step.

[0045] Four types of embodiments of the present invention that differ in the metal member will be described below, but the method for producing a nanocrystal film according to the present invention is not limited to the following four types of embodiments.

[0046] [First embodiment] As shown in (a) of FIG. 3, the metal member 100 according to the first embodiment of the present invention includes a first member 22a including a first metal and a second member 24 including a second metal. The first metal is a metal different from the second metal. The standard electrode potential of the first metal is higher than −2.00 V. The standard electrode potential of the second metal is also higher than −2.00 V. The standard electrode potential of the first metal is lower than the standard electrode potential of the second metal, and the difference between the standard electrode potentials of the first metal and the second metal is greater than 0.20 V. The first member 22a and the second member 24 are electrically connected. The second member 24 is disposed on the surface of the first member 22a, and the second member 24 has a predetermined pattern along the surface of the first member 22. For example, as shown in (a) of FIG. 3, the predetermined pattern of the second member 24 is a plurality of rectangles that extend along the surface of the first member 22 and are parallel to each other. However, the predetermined pattern of second member 24 is not limited to this and may be changed according to the design needs of the target nanocrystal film. For example, the predetermined pattern of second member 24 may be a wiring pattern such as straight lines or curves, a figure such as a polygon or circle, or a character.

[0047] As shown in FIG. 3B, in the light irradiation step, a nanocrystal film 25 having a predetermined pattern is formed on the surface of the second member 24. The predetermined pattern of the nanocrystal film 25 is the same as the pattern of the second member 24. That is, in the cases of FIG. 3A and FIG. 3B, the predetermined pattern of the nanocrystal film 25 is a plurality of rectangles that extend along the surface of the first member 22 and are parallel to each other. The nanocrystals contained in the nanocrystal film 25 include at least one of an oxide of a first metal and a hydroxide of the first metal. For example, as shown in FIG. 3B, the nanocrystal film 25 may have a hydroxide film 25a that covers a part or the entire surface of the second member 24, and oxide rods 25b (nanorods) that extend from the surface of the hydroxide film 25a. The position and orientation of the oxide rods 25b are not limited. For example, the oxide rods 25b may extend vertically from the hydroxide film 25a that covers the upper surface of the second member 24. The oxide rods 25b may extend laterally from the hydroxide film 25a covering the side surface of the second member 24. The hydroxide film 25a may be a hydroxide of the first metal, and the oxide rods 25b may be an oxide of the first metal. The nanocrystalline film 25 may consist only of an oxide of the first metal and a hydroxide of the first metal. The nanocrystalline film 25 may consist only of an oxide of the first metal. The nanocrystalline film 25 may consist only of a hydroxide of the first metal.

[0048] Hereinafter, nanocrystals containing at least one of an oxide of a first metal and a hydroxide of the first metal are referred to as "first nanocrystals". Nanocrystals containing at least one of an oxide of a second metal and a hydroxide of the second metal are referred to as "second nanocrystals". In the light irradiation step, the first nanocrystals may be preferentially (selectively) generated. One of the reasons for the preferential generation of the first nanocrystals is galvanic corrosion caused by the electrical connection between the first member and the second member. The mechanism by which the first nanocrystals are preferentially generated on the surface of the second member will be described below. Note that the mechanism by which the nanocrystals are generated in the first embodiment is not limited to the following mechanism.

[0049] When the first member and the second member are not electrically connected, in the light irradiation step, submerged photosynthesis of crystallites (SPSC) occurs on the surfaces of the first member and the second member. In general, SPSC is a method of forming nanocrystals on the surface of a metal member immersed in water by irradiating the surface of the metal member with light. When the first member and the second member are not electrically connected, first nanocrystals are generated on the surface of the first member by SPSC, and second nanocrystals are generated on the surface of the second member by SPSC. The mechanism of SPSC in the first member is common to the mechanism of SPSC in the second member. Below, a general metal corrosion reaction is explained, followed by an explanation of the mechanism of SPSC in the first member.

[0050] When a first member containing a first metal (M) is immersed in water, a reaction occurs in which the first metal corrodes. That is, the first metal is ionized in water, and as shown in the following reaction formula (1), the ions of the first metal (M n+ ) is produced. Generally, the corrosion reaction of a metal is a combination of an anodic reaction in which the metal becomes metal ions and dissolves, and a cathodic reaction in which an oxidant in the water is reduced. The reaction shown in the following reaction formula (1) is an anodic reaction. The reactions shown in the following reaction formulas (2) and (3) are both cathodic reactions. The reaction shown in the following reaction formula (2) occurs when the water is acidic. The reaction shown in the following reaction formula (3) occurs when the water is neutral or alkaline, or when the water contains dissolved oxygen. Here, when the standard electrode potential of the metal is positive, it is generally believed that the anodic reaction shown in the following reaction formula (1) does not occur. However, if hydrogen ions (H + Depending on the concentration of M or dissolved oxygen, the metal ions and react with M as shown in the following reaction formula (4). n+ The metal ions (M + For example, in water containing dissolved oxygen, hydroxide ions (OH -As a result, as shown in the following reaction formula (5), hydroxide (M(OH) n ) is then produced. As the water molecules leave the hydroxide, the oxide (MO x However, in the above-mentioned typical metal corrosion reaction, it is difficult to produce hydroxides and oxides with high crystallinity. In other words, the hydroxides and oxides produced in typical metal corrosion reactions are inferior in crystallinity to the nanocrystals obtained by the SPSC of the first embodiment. M→M n+ +ne - (1) 2H + +2e - →H2(2) O2+2H2O+4e - →4OH - (3) 2M+O2+2nH + →2M n+ +2H2O (4) M n+ +nOH - →M(OH) n (5) M(OH) n →MO x +(nx)H2O (6)

[0051] Hydroxide ions can be generated by reactions other than those of the above reaction formula (3). For example, hydroxide ions may be generated by dissociation of water molecules, or by using alkaline water. However, these hydroxide ions cannot be converted to hydroxide (M(OH) n ) and oxides (MO x The reaction in which this occurs is the general metal corrosion reaction described above. In this case, nanocrystals such as those obtained in the SPSC of the first embodiment are not formed.

[0052] In the first embodiment, it is assumed that nanocrystals are generated by the following mechanism using SPSC. When the first member and the second member are not electrically connected and the first nanocrystals are generated on the surface of the first member, the reactions shown in the above reaction formulas (1) to (5) first occur. Then, in the light irradiation step, the hydroxide of the first metal (M(OH) n ) to the oxide of the first metal (MO x ) grows on the surface of the first component. For example, the hydroxide of the first metal reacts with hydroxide ions (OH - ) to form the hydroxo complex ion ([M(OH) x ] y- ) is formed and redissolves in water. The higher the pH of the water, the easier it is for hydroxo complex ions to be generated. Then, at least a part of the hydroxo complex ions is transformed into nanocrystals. The nanocrystals contain at least one of a hydroxide and an oxide. For example, when the metal (M) is zinc (Zn), the reaction shown in the following reaction formula (7) produces tetrahydroxozincate(II) ions ([Zn(OH)4] 2- ) is generated. Then, ZnO nanocrystals are generated by the reaction shown in the following reaction formula (8). Here, the nanocrystals may be formed, for example, by light-induced tip growth. Light-induced tip growth means that the tip growth of columnar or needle-like crystals is promoted by light irradiation. The mechanism by which the nanocrystals are generated is not limited to the above reaction mechanism. Zn(OH)2+2OH - →[Zn(OH)4] 2- (7) [Zn(OH)4] 2- →ZnO+2OH - +H2O (8)

[0053] In the light irradiation step, when the water in which the metal member is immersed is irradiated with light, radiolysis of water may occur. The decomposition species include hydrogen radicals (H ), hydroxyl radicals ( OH ), and hydrated electrons (e aq - Of these, the hydroxyl radical reacts with the hydrated electron to produce the hydroxide ion (OH -In the light irradiation step, the reaction between the hydroxyl radicals and hydrated electrons may promote the production of hydroxide ions, thereby promoting the production of nanocrystals. In other words, in the light irradiation step, a photochemical reaction accompanied by the production of radicals may occur.

[0054] Next, the first member and the second member are electrically connected, and galvanic corrosion occurs, causing the first nanocrystals to be preferentially formed on the surface of the second member. The reaction mechanism is described below.

[0055] The standard electrode potential of the first metal contained in the first component is higher than -2.00V. The standard electrode potential of the second metal contained in the second component is higher than -2.00V. The standard electrode potential is the potential generated during the exchange of electrons in an oxidation-reduction reaction system in a liquid. The electrode reaction of each element in water and the standard electrode potential of each element are shown in Tables 1 and 2. The standard electrode potential is also used as a measure of the susceptibility of a metal to corrosion. Metals that are easily dissolved in water and easily ionized have a low standard electrode potential. By using the first metal and the second metal with a standard electrode potential higher than -2.00V, excessive reactions between the first metal and the second metal and water (direct reactions between the first metal and the second metal and water) can be suppressed. As a result, nanocrystals can be effectively produced by SPSC.

[0056] [Table 1]

[0057] [Table 2]

[0058] Galvanic corrosion occurs when two metals with different standard electrode potentials are brought into contact in water. Of the two metals, the metal with the lower standard electrode potential is called the "base metal". Of the two metals, the metal with the higher standard electrode potential is called the "noble metal". The corrosion rate of the base metal immersed in water together with the noble metal is greater than the corrosion rate of the base metal when only the base metal is immersed in water. The corrosion rate of the noble metal immersed in water together with the base metal is less than the corrosion rate of the noble metal when only the noble metal is immersed in water. In the first embodiment, the standard electrode potential of the first metal is lower than the standard electrode potential of the second metal. That is, the first metal is a base metal and the second metal is a noble metal. When the first metal is a base metal and the second metal is a noble metal, the first member containing the base first metal corrodes preferentially due to galvanic corrosion, and the first metal dissolves in water preferentially over the second metal. In other words, when metal M is a less noble first metal, the rate of the reaction shown in reaction formula (1) above increases due to galvanic corrosion.

[0059] Since the first and second members are electrically connected, the electrons (e - ) flow from the first member to the second member, and the cathodic reaction of the above reaction formula (2) or (3) occurs preferentially on the surface of the second member. In particular, when the water is neutral or alkaline, or when the water contains dissolved oxygen, the reaction shown in the above reaction formula (3) proceeds. As a result, hydroxide ions (OH - ) concentration increases, and the first metal ion (M n+ ) (the formation of the hydroxide of the first metal shown in the above reaction formula (5)) and the subsequent formation of the first nanocrystals by SPSC (the above reaction formulas (7) and (8)) are promoted. Meanwhile, the corrosion reaction of the second metal is suppressed by galvanic corrosion. In other words, when metal M is a noble second metal, the rate of the reaction shown in the above reaction formula (1) is decreased. As a result, the formation of the hydroxide of the second metal shown in the above reaction formula (5) and the subsequent formation of the second nanocrystals by SPSC are suppressed. Therefore, the first nanocrystals are preferentially formed on the surface of the second component.

[0060] In addition, the hydroxide ion (OH - ) can be generated by reactions other than the above reaction formula (3). For example, as shown in the following reaction formula (9), the electrons (e - ) at the interface between the second component and water is converted into hydrated electrons (e aq - ) is then converted into hydroxyl radicals (·OH) and hydrated electrons (e aq - ) produces hydroxide ions (OH - ) is generated near the surface of the second member. - ) concentration increases, and thus, in the same manner as described above, the formation of the hydroxide of the first metal according to reaction formula (5) above and the SPSC reaction according to reaction formulas (7) and (8) above proceed preferentially on the surface of the second component. e - →e aq - (9) OH+e aq - →OH - (10)

[0061] From the viewpoints of the reactivity of the first metal with water and the solubility of the ions of the first metal in water, the standard electrode potential of the first metal is preferably greater than -2.00 V and equal to or less than 1.00 V, more preferably -1.80 to 0.80 V, and even more preferably -1.70 to 0.60 V.

[0062] From the viewpoints of the reactivity of the second metal with water and the solubility of the second metal ions in water, the standard electrode potential of the second metal is preferably greater than -2.00 V and equal to or less than 1.60 V, more preferably -1.80 to 1.60 V, and even more preferably -1.70 to 1.60 V.

[0063] The first metal may be, for example, at least one selected from the group consisting of copper, bismuth, tungsten, lead, tin, molybdenum, nickel, cobalt, indium, cadmium, iron, zinc, chromium, ytterbium, niobium, vanadium, manganese, zirconium, titanium, aluminum, thorium, beryllium, and europium.

[0064] The second metal is selected from the group consisting of gold, platinum, iridium, palladium, silver, rhodium, copper, bismuth, tungsten, lead, tin, molybdenum, nickel, cobalt, indium, cadmium, iron, zinc, chromium, ytterbium, niobium, vanadium, manganese, zirconium, and titanium.

[0065] The combination of the first metal and the second metal is not particularly limited as long as the standard electrode potential of the first metal is lower than the standard electrode potential of the second metal and the difference between the standard electrode potentials of the first metal and the second metal is greater than 0.20 V. The combination of the first metal and the second metal may be, for example, zinc as the first metal and copper as the second metal. The first metal may be zinc and tungsten as the second metal. The first metal may be zinc and nickel as the second metal. The first metal may be zinc and silver as the second metal. The first metal may be aluminum and copper as the second metal. The first metal may be titanium and tungsten as the second metal.

[0066] The first member is not particularly limited as long as it is a member containing the first metal. The first member may be made of only the first metal. The first member may contain an oxide of the first metal in addition to the first metal (simple substance). However, a member made of only an oxide of the first metal does not correspond to the first member. From the viewpoint of nanocrystal growth, the content of the first metal in the first member is preferably 10.0 to 100.0 mass% based on the total mass of the first member, more preferably 15.0 to 100.0 mass%, and even more preferably 20.0 to 100.0 mass%. The higher the content of the first metal in the first member, the easier it is to generate an oxide or hydroxide and to control the composition of the oxide or hydroxide.

[0067] The second member is not particularly limited as long as it is a member containing the second metal. The second member may be made of only the second metal. The second member may contain an oxide of the second metal in addition to the second metal (simple substance). However, a member made of only an oxide of the second metal does not correspond to the second member. From the viewpoint of nanocrystal growth, the content of the second metal in the second member is preferably 10.0 to 100.0 mass% based on the total mass of the second member, more preferably 15.0 to 100.0 mass%, and even more preferably 20.0 to 100.0 mass%. The higher the content of the second metal in the second member, the easier it is to generate an oxide or hydroxide and to control the composition of the oxide or hydroxide.

[0068] The metal member may include an alloy. The first member may include an alloy of the first metal, or may consist only of an alloy of the first metal. The composition of the alloy of the first metal is not particularly limited. The alloy of the first metal may be, for example, an iron alloy, a copper alloy, a zinc alloy, etc. The second member may include an alloy of the second metal, or may consist only of an alloy of the second metal. The composition of the alloy of the second metal is not particularly limited as long as it contains the second metal. The alloy of the second metal may be, for example, an iron alloy, a copper alloy, a zinc alloy, etc. When the first metal is an alloy, the standard electrode potential of the first metal may be the standard electrode potential of the alloy. When the second metal is an alloy, the standard electrode potential of the second metal may be the standard electrode potential of the alloy.

[0069] Examples of iron alloys include Fe-C based alloys, Fe-Au based alloys, Fe-Al based alloys, Fe-B based alloys, Fe-Ce based alloys, Fe-Cr based alloys, Fe-Cr-Ni based alloys, Fe-Cr-Mo based alloys, Fe-Cr-Al based alloys, Fe-Cr-Cu based alloys, Fe-Cr-Ti based alloys, Fe-Cr-Ni-Mn based alloys, Fe-Cu based alloys, Fe-Ga based alloys, Fe-Ge based alloys, Fe-Mg based alloys, Fe-Mn based alloys, Fe-Mo based alloys, Fe-N based alloys, Fe-Nb based alloys, Fe-Ni based alloys, Fe-P based alloys, Fe-S based alloys, Fe-Si based alloys, Fe-Si-Ag based alloys, Fe-Si-Mg based alloys, Fe-Ti based alloys, Fe-U based alloys, Fe-V based alloys, Fe-W based alloys, and Fe-Zn based alloys.

[0070] Examples of copper alloys include Cu-Sn based alloys, Cu-Ni based alloys, Cu-Zn based alloys, Cu-P based alloys, Cu-Sn-P based alloys, Cu-Al based alloys, Cu-Zn-Sn based alloys, Cu-Zn-Mn based alloys, Cu-Zn-Si based alloys, Cu-Zn-Ni based alloys, Cu-Mn based alloys, Cu-Be based alloys, Cu-Ag based alloys, and Cu-Zr based alloys.

[0071] Examples of zinc alloys include Zn-Ni based alloys, Zn-Sb based alloys, Zn-Cu based alloys, Zn-Al based alloys, and Zn-Mg based alloys.

[0072] From the viewpoint of nanocrystal growth, the content of the first metal in the alloy of the first metal is preferably 10.0 to 99.8 mass%, more preferably 15.0 to 99.5 mass%, and even more preferably 20.0 to 99.9 mass%. From the viewpoint of nanocrystal growth, the content of the second metal in the alloy of the second metal is preferably 10.0 to 99.8 mass%, more preferably 15.0 to 99.5 mass%, and even more preferably 20.0 to 99.9 mass%.

[0073] The first component may further include other atoms that are inevitably mixed in. The content of the other atoms that are inevitably mixed in may be, for example, 3 mass% or less based on the total mass of the first component. From the viewpoint of nanocrystal growth, the content of the above atoms contained in the first component is preferably 1 mass% or less. The second component may further include other atoms that are inevitably mixed in. The content of the other atoms that are inevitably mixed in may be, for example, 3 mass% or less based on the total mass of the second component. From the viewpoint of nanocrystal growth, the content of the above atoms contained in the second component is preferably 1 mass% or less.

[0074] The shape of the first member is not particularly limited. Examples of the shape of the first member include a plate shape, a block shape, a round wire shape, a sheet shape, and a combination of these shapes. From the viewpoint of workability in immersing in water, the shape of the first member is preferably a plate shape, a block shape, or a sheet shape.

[0075] The method of forming the second member (the method of patterning the second member on the surface of the first member) is not particularly limited. For example, the second member may be formed on the entire surface of the first member by sputtering, vacuum deposition, pulse laser deposition (PLD), etc., and then the second member may be processed into a desired shape (pattern) by photolithography and a milling cutter, etc. The second member may be processed into a desired shape (pattern) by forming a photoresist pattern on the surface of the first member, subsequently depositing the second member on the surface of the first member, and subsequently removing the photoresist. The second member may be processed into an arbitrary pattern by depositing the second member on the entire surface of the first member, applying the photoresist to the second member, irradiating the photoresist with laser light, and partially removing the second member. The pattern of the second member may be deposited on the surface of the first member using a stencil mask. After forming the second member on the entire surface of the first member by electroless plating, a pulsed light or the like may be irradiated onto a predetermined portion of the second member, thereby adhering only the predetermined portion of the second member to the surface of the first member. A paste containing the second metal may be applied to the surface of the first member by screen printing, inkjet, or the like, and the paste may be sintered or hardened by heating or the like to form a pattern on the second member. In the above patterning method, the patterning conditions may be appropriately selected so as to prevent dissolution, corrosion, or peeling of the metal member by the chemical solution, and excessive oxidation of the metal member by heat treatment.

[0076] [Second embodiment] The second embodiment of the present invention will be described below. In the following, the description of matters common to the first and second embodiments will be omitted in some cases.

[0077] The metal member according to the second embodiment has a first member containing a first metal. The standard electrode potential of the first metal is higher than −2.00 V. The metal member according to the second embodiment may be composed of only the first member. The first member is a pattern structure having a predetermined pattern. As shown in FIG. 4, the predetermined pattern of the pattern structure 22b may be, for example, a mesh structure. In the light irradiation step, a nanocrystal film containing nanocrystals is formed on the surface of the first member (i.e., the pattern structure 22b). That is, in the light irradiation step, the nanocrystal film is formed on a part or the entire surface of the pattern structure 22b. That is, the nanocrystal film has a pattern similar to that of the pattern structure 22b. The nanocrystals contained in the nanocrystal film include at least one of an oxide of the first metal and a hydroxide of the first metal. The nanocrystal film may be composed of only an oxide of the first metal and a hydroxide of the first metal. The nanocrystal film may be composed of only an oxide of the first metal. The nanocrystal film may be composed of only a hydroxide of the first metal. Since the metal member 110 (first member) according to the second embodiment is a pattern structure 22b, there is no need to prepare the metal member before the light exposure process, and there is no need to perform a separate patterning process (photolithography, etc.) after the formation of the nanocrystal film.

[0078] As described below, the inventors speculate that the mechanism for generating a nanocrystalline film in the second embodiment is similar to that in the first embodiment, except that the second member is not used.

[0079] By irradiating the surface of the first member (pattern structure) immersed in water with light, the reactions shown in the above reaction formulas (1) to (5) occur, and the hydroxide of the first metal (M(OH) n ) is generated on the surface of the pattern structure. The tips of the nanocrystals then grow according to the reactions shown in the above reaction formulas (7) and (8). Note that the reactions in the above reaction formulas (7) and (8) are for the case where the first metal M is zinc, but may occur for other first metals.

[0080] The pattern structure is a member containing a first metal and processed into a two-dimensional or three-dimensional pattern. The pattern structure may have at least one of a mesh structure and a lattice structure. The pattern structure 22b shown in FIG. 4 is a sample stage (sample mesh) used for observation with a transmission electron microscope. The sample mesh for a transmission electron microscope is a metal that has been subjected to mesh processing, and is preferably used as the pattern structure (first member).

[0081] The pattern structure may be manufactured by existing methods such as plain weaving of wires made of the first metal, punch press, photoetching, etc. Alternatively, the pattern structure may be manufactured by forming a structure having a predetermined pattern using a material other than the first metal, and coating the surface of the structure with the first metal by a method such as plating.

[0082] The predetermined pattern of the pattern structure is not particularly limited. For example, as shown in Fig. 4 and Fig. 5 (a), the pattern structure 22b may have a mesh structure. As shown in Fig. 5 (b), the pattern structure 22b may have a plurality of circular holes having the same inner diameter formed at equal intervals. As shown in Fig. 5 (c), the pattern structure 22b may have a honeycomb structure in which a plurality of hexagonal holes having the same size are formed at equal intervals.

[0083] The standard electrode potential of the first metal contained in the pattern structure (first member) is preferably greater than -2.00 V and less than 1.00 V, more preferably -1.80 to 0.80 V, and even more preferably -1.70 to 0.60 V, from the viewpoints of the reactivity of the first metal with water and the solubility of the ions of the first metal in water.

[0084] The first metal contained in the pattern structure (first member) may be, for example, at least one selected from the group consisting of copper, bismuth, tungsten, lead, tin, molybdenum, nickel, cobalt, indium, cadmium, iron, zinc, chromium, ytterbium, niobium, vanadium, manganese, zirconium, titanium, aluminum, thorium, beryllium, and europium.

[0085] The pattern structure (first member) may contain an alloy of the first metal, or may be made of only an alloy of the first metal. The composition of the alloy of the first metal is not particularly limited. The alloy of the first metal may be, for example, an iron alloy, a copper alloy, a zinc alloy, etc.

[0086] From the viewpoint of nanocrystal growth, the content of the first metal in the pattern structure (first member) is preferably 10.0 to 100.0 mass% based on the total mass of the first member, more preferably 15.0 to 100.0 mass%, and even more preferably 20.0 to 100.0 mass%. The higher the content of the first metal in the pattern structure, the easier it is for an oxide or hydroxide to be generated on the surface of the pattern structure, and the easier it is to control the composition of the oxide or hydroxide.

[0087] The composition of the pattern structure (first member) may be the same as the composition of the first member in the first embodiment.

[0088] [Third embodiment] The following describes the third embodiment of the present invention. In the following, descriptions of matters common to the first, second and third embodiments may be omitted in some cases.

[0089] As shown in FIG. 6 and FIG. 7, the metal member 130 according to the third embodiment includes a first member 22c containing a first metal, a substrate 26, and a conductive film 28 disposed on the surface of the substrate 26. The standard electrode potential of the first metal is higher than −2.00 V. The first member 22c and the conductive film 28 are electrically connected by a wiring material 30. The conductive film 28 has a predetermined pattern along the surface of the substrate 26. In the light irradiation step, a nanocrystal film is formed on a part or the entire surface of the conductive film 28. That is, the nanocrystal film has the same pattern as the conductive film 28. The nanocrystals contained in the nanocrystal film include at least one of an oxide of the first metal and a hydroxide of the first metal. The nanocrystal film may be composed only of an oxide of the first metal and a hydroxide of the first metal. The nanocrystal film may be composed only of an oxide of the first metal. The nanocrystal film may be composed only of a hydroxide of the first metal.

[0090] As described below, the inventors speculate that the nanocrystal generation mechanism in the third embodiment is similar to that in the first embodiment, except that the conductive film has an electrochemical function equivalent to that of the second member.

[0091] The reaction shown in the above reaction formula (1) occurs in water, and the first metal in the first component is converted into a first metal ion (M n+ ) and electrons (e - Since the first member and the conductive film are electrically connected, electrons (e - ) flow from the first member into the conductive membrane, and the cathodic reaction shown in the above reaction formula (2) or (3) occurs preferentially on the surface of the conductive membrane. In particular, when the water is neutral or alkaline, or when the water contains dissolved oxygen, the reaction shown in the above reaction formula (3) proceeds. As a result, hydroxide ions (OH - ) concentration increases, and hydroxide ions (OH - ) and the first metal ion (M n+) (the production of the hydroxide of the first metal shown in the above reaction formula (5)) and the subsequent production of the first nanocrystals by SPSC (the reactions shown in the above reaction formulas (7) and (8)) are promoted. At this time, the corrosion reaction of the conductive film is suppressed by galvanic corrosion.

[0092] The hydroxide ion (OH - ) can be generated by a reaction other than that of the above reaction formula (3). For example, as shown in the above reaction formula (9), the electrons (e - ) at the interface between the conductive film and water. aq - ) is then converted into hydroxyl radicals (·OH) and hydrated electrons (e aq - ) produces hydroxide ions (OH - ) is generated near the surface of the conductive film. - ) increases, the formation of the hydroxide of the first metal according to reaction formula (5) above and the SPSC reactions according to reaction formulas (7) and (8) above proceed preferentially on the surface of the conductive film.

[0093] From the viewpoints of the reactivity of the first metal with water and the solubility of the ions of the first metal in water, the standard electrode potential of the first metal is preferably greater than -2.00 V and equal to or less than 1.00 V, more preferably -1.80 to 0.80 V, and even more preferably -1.70 to 0.60 V.

[0094] The first metal may be, for example, at least one selected from the group consisting of copper, bismuth, tungsten, lead, tin, molybdenum, nickel, cobalt, indium, cadmium, iron, zinc, chromium, ytterbium, niobium, vanadium, manganese, zirconium, titanium, aluminum, thorium, beryllium, and europium.

[0095] The first member may include an alloy of the first metal, or may be made of only an alloy of the first metal. The composition of the alloy of the first metal is not particularly limited. The alloy of the first metal may be, for example, an iron alloy, a copper alloy, a zinc alloy, or the like.

[0096] From the viewpoint of nanocrystal growth, the content of the first metal in the first component is preferably 10.0 to 100.0 mass% based on the total mass of the first component, more preferably 15.0 to 100.0 mass%, and even more preferably 20.0 to 100.0 mass%. The higher the content of the first metal in the first component, the easier it is to generate an oxide or hydroxide, and the easier it is to control the composition of the oxide or hydroxide.

[0097] The composition of the first member of the third embodiment may be the same as the composition of the first member of the first embodiment.

[0098] The material of the substrate on which the conductive film is formed is not particularly limited. The substrate may be at least one selected from the group consisting of glass, ceramics, metals covered with an insulating material, semiconductors covered with an insulating material, and plastics. The substrate may be a resin film selected from the group consisting of polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyarylate (PAR), polyethersulfone (PES), polycarbonate (PC), and polyimide (PI), or a combination thereof. The material of the substrate may be appropriately selected depending on the properties required for the device to which the nanocrystal film pattern is applied (e.g., transparency, dimensional stability, solvent resistance, heat resistance, gas barrier properties, and moisture absorption resistance), reactivity with water, and adhesion to the conductive film.

[0099] It is preferable that the nanocrystalline film is not formed on the surface of the substrate. In other words, it is preferable that the pattern of the nanocrystalline film is selectively formed only on the surface of the conductive film out of the surface of the conductive film and the surface of the substrate itself. By suppressing the flow of electrons generated in the first component into the substrate itself, the formation of the nanocrystalline film on the surface of the substrate is suppressed. From this viewpoint, the volume resistivity of the substrate is 1×10 1It is preferable that the resistance is Ωcm or more, and 1×10 2 More preferably, it is 1×10 3 It is more preferable that the resistivity is Ωcm or more.

[0100] The conductive film may include at least one selected from the group consisting of copper, silver, gold, platinum, aluminum, chromium, nickel, iron, tin, lead, indium tin oxide (ITO), fluorine-doped tin oxide (FTO), and aluminum-doped zinc oxide. The conductive film may be equivalent to the second member in electrochemical function. That is, the conductive film may include a second metal, the standard electrode potential of the second metal may be higher than -2.00V, the standard electrode potential of the first metal may be lower than the standard electrode potential of the second metal, and the difference between the standard electrode potentials of the first metal and the second metal may be greater than 0.20V. The composition of the conductive film may be the same as that of the second member of the first embodiment.

[0101] The method of forming the conductive film (the method of patterning the conductive film on the surface of the substrate) is not particularly limited. For example, the conductive film may be formed on the entire surface of the substrate by sputtering, vacuum deposition, pulse laser deposition (PLD), etc., and then the conductive film may be processed into a desired shape (pattern) by photolithography and a milling cutter, etc. The conductive film may be processed into a desired shape (pattern) by forming a photoresist pattern on the surface of the substrate, then depositing the conductive film on the surface of the substrate, and then removing the photoresist. The conductive film may be processed into an arbitrary pattern by forming the conductive film on the entire surface of the substrate, applying a photoresist to the substrate, irradiating the photoresist with laser light, and partially removing the conductive film. The conductive film may be deposited on the surface of the substrate using a stencil mask. The conductive film may be formed on the entire surface of the substrate by electroless plating, and then irradiating a predetermined portion of the conductive film with pulse light, etc., to adhere only the predetermined portion of the conductive film to the surface of the substrate. A paste containing the raw materials of the conductive film may be applied to the surface of the base material by screen printing, inkjet printing, or the like, and the paste may be sintered or cured by heating or the like to form a conductive film pattern.

[0102] The electrons (e - ) flows into the conductive film and the growth of nanocrystals by the SPSC reaction is promoted on the surface of the conductive film, so that the volume resistivity of the conductive film is not particularly limited. From the viewpoint of uniformity of nanocrystal growth, the volume resistivity of the conductive film is, for example, 1×10 0 It is preferable that the resistance is Ωcm or less, and 1×10 -1 More preferably, it is 1×10 -2 It is more preferable that the resistivity is Ωcm or less.

[0103] The method of electrically connecting the first member and the conductive film is not particularly limited. For example, the first member and the conductive film may be electrically connected via a conductive material. The electrical connection between the first member and the conductive film does not mean an electrical connection via water. The first member and the substrate may be electrically connected as long as the generation of the nanocrystalline film on the surface of the substrate itself is suppressed.

[0104] The arrangement of the first member and the substrate in the metal member is not particularly limited. From the viewpoint of workability and nanocrystalline film generation, the arrangement of the first member and the substrate in the metal member is preferably the arrangement shown in FIG. 6 or FIG. 7. As shown in FIG. 6, the first member 22c and the substrate 26 may be electrically connected via the wiring material 30, and the conductive film 28 arranged on the surface of the substrate 26 may be electrically connected to the wiring material 30. In the case of FIG. 6, one end of the wiring material 30 is wound around the first member 22c, and the other end of the wiring material 30 is wound around the substrate 26. As shown in FIG. 7, the wiring material 30 may be composed of a metal wire 32 and a brazing material 34 connected to both ends of the metal wire 32. The brazing material 34 may be solder. In the case of FIG. 7, one end of the metal wire 32 is connected to the first member 22c via the brazing material 34, and the other end of the metal wire 32 is connected to the substrate 26 and the conductive film 28 via another brazing material 34.

[0105] The wiring material 30 that connects the first member 22c and the conductive film 28 may include at least one selected from the group consisting of copper, silver, gold, platinum, aluminum, chromium, nickel, iron, tin, and lead.

[0106] The solder may be Sn-Pb solder, Sn-Pb-Ag solder, Sn-Ag-Cu solder, etc. Considering the impact on the environment, the solder is preferably Sn-Ag-Cu solder that is substantially free of lead. When using the solder to make an electrical connection, the solder may be heated to a temperature equal to or higher than the melting point. Specifically, when the solder is Sn-Pb solder, the solder may be heated to a temperature range of 230 to 300°C to melt the solder.

[0107] When multiple conductive film patterns are arranged on the surface of the substrate, it is preferable that the multiple conductive film patterns are not electrically independent from each other. In other words, it is preferable that the multiple conductive film patterns are electrically connected to each other. As shown in FIG. 8, the conductive film 28 may be one continuous pattern. This allows electrons generated in the first member 22c to spread throughout the entire conductive film 28 via the wiring material 30, and a nanocrystalline film is generated uniformly over the entire surface of the conductive film 28.

[0108] [Fourth embodiment] The fourth embodiment of the present invention will be described below. In the following, descriptions of matters common to the first, second, third and fourth embodiments will be omitted in some cases.

[0109] As shown in (a), (b), and (c) of FIG. 9 and (a), (b), and (c) of FIG. 10, the metal members 140 and 150 according to the fourth embodiment include a first member 22d containing a first metal and a mask material 36 overlapping the surface of the first member 22d. Water is interposed between the first member 22d and the mask material 36. The standard electrode potential of the first metal is higher than −2.00 V. An exposed portion 90 of the surface of the first member 22d that does not overlap with the mask material 36 has a predetermined pattern along the surface of the first member 22d.

[0110] 9(a), (b), and (c), the exposed portion 90 that does not overlap with the mask material 36 has a pattern of a plurality of squares arranged in a lattice at equal intervals along the surface of the first member 22d. In other words, the mask material 36 has a mesh structure or a lattice structure composed of a plurality of vertical line portions arranged in parallel at equal intervals and horizontal line portions arranged in parallel at equal intervals, and the exposed portion 90 of the first member 22d is located directly below the area surrounded by the vertical line portions and the horizontal line portions.

[0111] 10(a), (b), and (c), the exposed portion 90 that does not overlap with the mask material 36 has a pattern of multiple strips (rectangular) that are equally spaced and parallel to the surface of the first member 22d. In other words, the mask material 36 is composed of multiple cylindrical members that are equally spaced and parallel to each other, and the exposed portion 90 of the first member 22d is located directly below the region between the cylindrical members. The cylindrical members may be referred to as rod-shaped members or wires.

[0112] As shown in (c) of Fig. 9 and (c) of Fig. 10, in the light irradiation step, nanocrystalline film 25 having a predetermined pattern is formed on the surface of exposed portion 90 irradiated with light. The predetermined pattern of nanocrystalline film 25 is the same as the pattern of exposed portion 90. In other words, the predetermined pattern of nanocrystalline film 25 shown in (c) of Fig. 9 is a pattern of a plurality of squares arranged in a lattice shape at equal intervals along the surface of first member 22d. The predetermined pattern of nanocrystalline film 25 shown in (c) of Fig. 10 is a pattern of a plurality of stripes arranged in parallel at equal intervals along the surface of first member 22d.

[0113] The nanocrystals contained in the nanocrystal film 25 include at least one of an oxide of the first metal and a hydroxide of the first metal. As shown in (c) of FIG. 9 and (c) of FIG. 10, the nanocrystal film 25 may have a hydroxide film 25a covering the exposed portion 90 of the first member 22d and oxide rods 25b (nanorods) extending from the surface of the hydroxide film 25a. The hydroxide film 25a may be a hydroxide of the first metal, and the oxide rods 25b may be an oxide of the first metal. The nanocrystal film 25 may be composed only of an oxide of the first metal and a hydroxide of the first metal. The nanocrystal film 25 may be composed only of an oxide of the first metal. The nanocrystal film 25 may be composed only of a hydroxide of the first metal.

[0114] The present inventors speculate that the mechanism of nanocrystal generation in the fourth embodiment is as follows. In the following, the region where water is present between the first member 22d and the mask material 36 or the surface of the first member 22d located in this region is referred to as a "gap portion" (gap portion 94). The gap portion 94 is a portion of the surface of the first member 22d that is not irradiated with light. The exposed portion 90 irradiated with light may also be referred to as a "light irradiated portion (90)."

[0115] In the gap 94, the metal (M) is dissolved in the water and becomes a metal ion (M n+ The reaction of the above reaction formula (1) proceeds in the gap 94 for the following two reasons.

[0116] The first reason is an increase in electron density in the light-irradiated portion (90). When light, which is an electromagnetic wave, is incident on the surface of the exposed portion 90 containing the first metal, an oscillating electric field is generated in the first metal. This electric field accelerates free electrons in the first metal, and the electron density in the light-irradiated portion (90) becomes higher than that in the gap portion 94 where light is not irradiated. As a result, a local potential difference occurs between the light-irradiated portion (90) and the gap portion 94, and the reaction of the above reaction formula (1) proceeds in the gap portion 94 to fill this difference.

[0117] The second reason is the difference in oxygen concentration between the light-irradiated portion (90) and the gap portion 94. In the gap portion 94, the supply of oxygen from the water tends to be insufficient, and a kind of oxygen concentration cell is formed between the light-irradiated portion (90) and the gap portion 94. As a result, the reaction shown in the above reaction formula (3) proceeds in the light-irradiated portion (90) so as to reduce the oxygen concentration. Accordingly, the reaction shown in the above reaction formula (1) proceeds in the gap portion 94.

[0118] As the reaction of the above reaction formula (3) proceeds in the light irradiation portion (90), hydroxide ions (OH - ) concentration increases. - ) and the ions of the first metal (M n+ ) (reaction of reaction formula (5) above) proceeds in the light irradiated portion (90). That is, a hydroxide of the first metal is formed on the surface of the light irradiated portion (90). Then, the production of first nanocrystals by SPSC (reactions of reaction formulas (7) and (8) above) is promoted in the light irradiated portion (90). Note that the reactions of reaction formulas (7) and (8) above are reactions when the first metal M is zinc, but may occur when other first metals are used.

[0119] In addition, the hydroxide ion (OH - ) may be generated by a reaction other than that of the above reaction formula (3). For example, as shown in the above reaction formula (9), electrons (e - ) at the interface between the light irradiated portion (90) and water is converted into hydrated electrons (e aq - ) is then converted into hydroxyl radicals (·OH) and hydrated electrons (e aq - ) produces hydroxide ions (OH - ) is generated in the vicinity of the light irradiation section (90). - ) increases, the formation of the hydroxide of the first metal according to reaction formula (5) above and the SPSC reactions according to reaction formulas (7) and (8) above proceed preferentially on the surface of the light irradiated portion (90).

[0120] From the viewpoints of the reactivity of the first metal with water and the solubility of the ions of the first metal in water, the standard electrode potential of the first metal is preferably greater than -2.00 V and equal to or less than 1.00 V, more preferably -1.80 to 0.80 V, and even more preferably -1.70 to 0.60 V.

[0121] The first metal may be, for example, at least one selected from the group consisting of copper, bismuth, tungsten, lead, tin, molybdenum, nickel, cobalt, indium, cadmium, iron, zinc, chromium, ytterbium, niobium, vanadium, manganese, zirconium, titanium, aluminum, thorium, beryllium, and europium.

[0122] The first member may include an alloy of the first metal, or may be made of only an alloy of the first metal. The composition of the alloy of the first metal is not particularly limited. The alloy of the first metal may be, for example, an iron alloy, a copper alloy, a zinc alloy, or the like.

[0123] From the viewpoint of nanocrystal growth, the content of the first metal in the first component is preferably 10.0 to 100.0 mass% based on the total mass of the first component, more preferably 15.0 to 100.0 mass%, and even more preferably 20.0 to 100.0 mass%. The higher the content of the first metal in the first component, the easier it is to generate an oxide or hydroxide, and the easier it is to control the composition of the oxide or hydroxide.

[0124] The composition of the first member of the fourth embodiment may be the same as the composition of the first member of the first embodiment.

[0125] The area of ​​the exposed portion 90 of the surface of the first member 22d is represented as S1. The area of ​​the overlapping portion 92 of the surface of the first member 22d where the mask material 36 overlaps is represented as S2. The overlapping portion 92 is a region (non-irradiated portion) of the surface of the first member 22d that is not irradiated with light. Metal ions (M n+From the viewpoints of the amount of elution of ), uniformity of growth of nanocrystals, etc., the area ratio S2 / S1 is preferably 1 / 200 to 1 / 2, more preferably 1 / 150 to 1 / 2.5, and even more preferably 1 / 100 to 1 / 3.

[0126] The method of forming the gap 94 between the surface of the first member 22d and the mask material 36 is not particularly limited. For example, the mesh-shaped mask material 36 may be disposed on the surface of the first member 22d via a spacer having a predetermined dimension. A convex portion functioning as a spacer may be present on a part of the surface of the mask material 36, or only the convex portion of the surface of the mask material 36 may contact the surface of the first member 22d. As shown in (a) and (b) of FIG. 10, the gap 94 may be formed by a part of the surface of the rod-shaped mask material 36 contacting the surface of the first member 22d. A linear mask material may be wound around the surface of the first member 22d via a spacer. As shown in (b) of FIG. 9, the entire surface of the first member 22d and the entire mask material 36 may be completely separated from each other. As shown in (b) of FIG. 10, a part of the mask material 36 may contact the first member 22d.

[0127] From the viewpoints of facilitating the elution of ions of the first metal and workability, the distance between the surface of the first member 22d and the mask material 36 (the width of the gap 94) is preferably 50 μm or less, more preferably 40 μm or less, and even more preferably 30 μm or less. However, the width of the gap 94 may be greater than these upper limits in some parts.

[0128] The material of the mask material 36 is not particularly limited as long as it is not easily dissolved or deteriorated in water and can maintain a desired shape. The mask material 36 may be a conductive material or a non-conductive material.

[0129] The following points are common to the first, second, third and fourth embodiments.

[0130] (Light irradiation method) As shown in FIG. 1, the water 2 and the metal member 100 may be contained in a container 6a. The container 6a may include a container body 8a that contains the water 2 and the metal member 100, and a lid body 10a. The container 6a may not include the lid body 10a. The lid body 10a may seal the container body 8a. Light L may be irradiated using a lamp (light source) 12. By using the lamp 12, light of a certain intensity can be irradiated onto the surface of the metal member 100. The position of the lamp 12 may be appropriately adjusted so that nanocrystals are effectively generated. When irradiating with sunlight, the lamp 12 may not be used. When irradiating with sunlight, the position and orientation of the container 6a may be appropriately adjusted so that the surface of the metal member 100 is irradiated with sunlight.

[0131] The metal member 100 may be arranged so that the surface onto which light is irradiated is vertical as shown in FIG. 1, or may be arranged so that the surface onto which light is irradiated is horizontal as shown in FIG.

[0132] The distance from the water surface to the light irradiation surface of the metal member 100 can be appropriately set depending on the type of metal member and water, and is not particularly limited. The distance may be, for example, 5 mm to 10 m. From the viewpoint of suppressing the decrease in effect due to light scattering and promoting the growth of nanocrystals, the distance is preferably 5 mm to 8 m, and more preferably 5 mm to 5 m.

[0133] The shape of the container body 8a is not particularly limited. The shape of the container body 8a may be a rectangular parallelepiped like the container body 8a shown in Fig. 6, or may be a cylindrical shape like the container body 8b included in the container 6b shown in Fig. 2. The shape of the container body 8a may be appropriately selected so that the light can be effectively irradiated onto the surface of the metal member 100.

[0134] The shape of the lid body 10a is not particularly limited. The shape of the lid body 10a may be a rectangular parallelepiped like the lid body 10a shown in Fig. 1, or may be a cylindrical shape like the lid body 10b shown in Fig. 2. The shape of the lid body 10a may be any shape that allows the light to be effectively irradiated onto the surface of the metal member 100.

[0135] The material of the container 6a (container body 8a and lid body 10a) is not particularly limited as long as it does not block the light from being irradiated onto the surface of the metal member 100. The material of the container body 8a and the lid body 10a is preferably one that does not react with water. The material of the container body 8a and the lid body 10a may be, for example, glass, plastic, etc.

[0136] (About the wavelength of light) The wavelength of the light used in the light irradiation process is not particularly limited. The wavelength of the light may be shorter than that of infrared light. For example, the wavelength of the light may be 1000 nm or less. In the spectrum of the light used in the light irradiation process, the wavelength at which the intensity is maximum may be 360 ​​nm or more and less than 620 nm. The spectrum of light may be rephrased as the spectral radiant distribution of light, and the intensity may be rephrased as the spectral irradiance or spectral irradiance. In other words, in the spectral radiant distribution (spectrum) of the light used in the light irradiation process, the wavelength at which the spectral irradiance (intensity) is maximum may be 360 ​​nm or more and less than 620 nm. The unit of the spectral irradiance (intensity) of light is, for example, W·m -2 nm -1 In the wavelength region of 360 nm or more and less than 620 nm, the composition of oxides and hydroxides generated from the metal member and water can be easily controlled by adjusting the wavelength of the light irradiated to the metal member. Therefore, nanocrystals with high crystallinity can be easily obtained. The crystallinity (degree of crystallinity) of the nanocrystals can be confirmed, for example, by X-ray diffraction (XRD) analysis. The composition of the oxides and hydroxides can be confirmed, for example, by point analysis using energy dispersive X-ray analysis (EDX). When the wavelength is 620 nm or more, it is difficult to obtain nanocrystals. When the wavelength is less than 360 nm, the nanocrystals are easily decomposed and the shape of the nanocrystals is easily distorted. The present inventors speculate that the reason why the nanocrystals are easily decomposed when the wavelength is less than 360 nm is as follows.

[0137] When the wavelength is less than 360 nm, if the nanocrystal is a semiconductor, the nanocrystal may act as a photocatalyst when irradiated with light. When the nanocrystal acts as a photocatalyst, as described below, photolysis of water occurs, generating hydrogen gas and oxygen gas. As a result, the formed oxide returns to hydroxide, and the nanocrystal is decomposed. In addition, when the wavelength is less than 360 nm, energy is easily converted to heat, so energy efficiency is easily reduced, and metal members are easily damaged by heat. From the viewpoint of easily obtaining the above effects due to the wavelength, the wavelength with the maximum intensity in the spectrum of light used in the light irradiation step is preferably 380 to 600 nm, and more preferably 400 to 580 nm. From the viewpoint of efficiency of radiolysis of water, equipment constraints, band gaps of oxides and hydroxides, and prevention of generation of thermal energy (heat generation) when excited electrons are relaxed, the wavelength may be appropriately adjusted within the above range.

[0138] The light source of the light irradiated to the metal member is not particularly limited as long as it can irradiate the above light. The light source may be, for example, the sun, an LED, a xenon lamp, a mercury lamp, a fluorescent lamp, or the like. The light irradiated to the metal member may be, for example, sunlight or simulated sunlight. Sunlight is favorably used from the viewpoint that it falls endlessly on the earth and can be used as a renewable energy source that does not emit greenhouse gases. The simulated sunlight means light that does not use the sun as a light source and whose spectrum matches the spectrum of sunlight. The simulated sunlight can be emitted by, for example, a solar simulator using a metal halide lamp, a halogen lamp, or a xenon lamp. The simulated sunlight is generally used for the purpose of evaluating the strength of materials against ultraviolet rays, evaluating solar cells, or evaluating weather resistance. The simulated sunlight can also be favorably used in this embodiment.

[0139] In the light irradiation step, light may be irradiated to the interface where the surface of the metal member is in contact with water. The interface can be obtained, for example, by immersing the metal member in water, or by circulating water through a part or the whole of the metal member. In the light irradiation step, it is preferable to immerse the metal member below the water surface from the viewpoint of the growth of nanocrystals.

[0140] (Details of nanocrystals) As described above, the nanocrystal film formed in the light irradiation step contains the metal (e.g., the first metal) originally contained in the metal member. The nanocrystals contain at least one of an oxide and a hydroxide. The nanocrystals may be composed of an oxide and a hydroxide, or may be composed only of an oxide, or may be composed only of a hydroxide.

[0141] At least one of the oxide and hydroxide is preferably a semiconductor. That is, the nanocrystal preferably contains a semiconductor. The nanocrystal may be composed of only a semiconductor. When the nanocrystal contains a semiconductor, the nanocrystal can be applied to semiconductor devices such as photocatalysts, luminescent materials, solar cells, quantum computers, and biosensors.

[0142] The semiconductor may include at least one of a p-type semiconductor and an n-type semiconductor. That is, the nanocrystal may include at least one of a p-type semiconductor and an n-type semiconductor. When the nanocrystal includes at least one of a p-type semiconductor and an n-type semiconductor, the electrical conductivity of the nanocrystal (semiconductor) is improved, and the range of application of the nanocrystal to the semiconductor device is expanded.

[0143] Oxide Semiconductors (MO x ) may become a p-type or n-type semiconductor when an oxide semiconductor is doped with an impurity element or when the ratio of metal to oxygen deviates from the stoichiometric composition. When the ratio of metal to oxygen deviates from the stoichiometric composition, oxygen in the oxide semiconductor is lost, and the composition of the oxide semiconductor becomes MO. x-nAs a result, the oxide semiconductor becomes n-type. When an oxide semiconductor takes in excess oxygen, the composition of the oxide semiconductor becomes MO x+n The metal atom vacancies act as holes, making the oxide semiconductor p-type.

[0144] The p-type semiconductor may be at least one selected from the group consisting of copper oxide (I) (CuO), copper oxide (II) (CuO), silver oxide (I) (AgO), nickel oxide (II) (NiO), iron oxide (III) (FeO), tungsten oxide (VI) (WO), and tin oxide (II) (SnO).

[0145] The n-type semiconductor may be at least one selected from the group consisting of iron (III) oxide (Fe2O3), indium (III) oxide (In2O3), tungsten (VI) oxide (WO3), lead (II) oxide (PbO), vanadium (V) oxide (V2O5), niobium (III) oxide (Nb2O3), titanium (IV) oxide (TiO2), zinc (II) oxide (ZnO), tin (IV) oxide (SnO2), aluminum (III) oxide (Al2O3), and zirconium (IV) oxide (ZrO2).

[0146] Some of the oxides mentioned above can be either p-type or n-type semiconductors. For example, iron oxide (III) (Fe2O3) is usually prone to oxygen deficiency, so iron oxide (III) behaves as an n-type semiconductor. However, when iron oxide (III) is doped with nitrogen (N), iron oxide (III) can become p-type. In tungsten oxide (VI) (WO3), either the metal (W) or oxygen can be deficient. When the metal (W) is deficient, tungsten oxide (VI) is a p-type semiconductor. When the oxygen is deficient, tungsten oxide (VI) is an n-type semiconductor.

[0147] The shape of the nanocrystal may be at least one selected from the group consisting of needle-like, columnar, rod-like, tubular, scale-like, block-like, flower-like, starfish-like, branch-like and convex shapes. The flower-like shape means a shape in which multiple columnar crystals extend radially from the center of the crystal. The starfish-like shape means a shape in which multiple columnar crystals extend approximately equally spaced from the center of the crystal in the same plane.

[0148] The maximum width (e.g., length) of the nanocrystals may be 2 nm to 10 μm, or 2 nm to 1000 nm. The maximum width of the nanocrystals implies the maximum width of an aggregate of a plurality of nanocrystals. The height of the nanocrystals from the surface of the metal member is not particularly limited. The nanocrystals may have a solid structure or a hollow structure. The thickness of the nanocrystal film may be 2 nm to 10 μm, or 2 nm to 1000 nm.

[0149] (About water) The water in which the metal member is immersed may include at least one selected from the group consisting of pure water, ion-exchanged water, rainwater, tap water, river water, well water, filtered water, distilled water, reverse osmosis water, spring water, spring water, dam water, and seawater. The water may be water whose pH has been adjusted by including at least one of an acid and a base (i.e., an aqueous solution of at least one of an acid and a base). From the viewpoint of controlling the composition of nanocrystals and productivity, the water is preferably pure water, ion-exchanged water, or tap water. However, as water of natural origin, river water, well water, dam water, seawater, etc. may also be suitably used.

[0150] The pH of the water may be 5.00 to 10.0. By setting the pH to 5.00 or more, the formation of nanocrystals under light irradiation can be promoted. Furthermore, by setting the pH to 10.0 or less, the workability during nanocrystal film formation is improved. From the viewpoint of controlling the composition of nanocrystals, the pH of the water is preferably 5.5 to 9.5, and more preferably 6.0 to 9.0.

[0151] The pH of the water may be measured, for example, by a pH meter manufactured by Horiba, Ltd. (LAQUAact, a portable pH meter / water quality meter).

[0152] The electrical conductivity of the water may be 80000 μS / cm or less. From the viewpoint of increasing the crystallinity of the nanocrystals, the electrical conductivity of the water is preferably 10000 μS / cm or less, more preferably 5000 μS / cm or less, and even more preferably 1.0 μS / cm or less. The lower limit of the electrical conductivity of the water may be, for example, 0.05 μS / cm.

[0153] The electrical conductivity of the water may be measured, for example, by a pH meter manufactured by Horiba, Ltd. (LAQUAact, a portable pH meter / water quality meter).

[0154] The purity of water is not particularly limited. The purity of water means the mass ratio of water molecules contained in water. The purity of water may be, for example, 80.0 mass% or more based on the total mass of water. By making the purity of water 80.0 mass% or more, the influence of impurities under light irradiation can be suppressed. Examples of the influence of impurities include precipitation of salt and formation of a passive film. From the viewpoint of controlling the composition of nanocrystals, the purity of water is preferably 85.0 mass% or more, and more preferably 90.0 mass% or more. The upper limit of the purity of water may be, for example, 100.0 mass%.

[0155] The purity of water can sometimes be controlled by the electrical conductivity. For example, when the type of solute (impurity) dissolved in water is specified and the purity of the water is within the above range, the concentration of the solute and the electrical conductivity are often proportional to each other. On the other hand, when water contains multiple solutes (impurities), it is difficult to determine the purity of the water from the electrical conductivity value even if the electrical conductivity is measured. It is preferable to control the purity of water by the electrical conductivity of the water.

[0156] The concentration of dissolved oxygen in water is not particularly limited. From the viewpoint of promoting the growth reaction of nanocrystals by light irradiation, the concentration of dissolved oxygen in water is, for example, based on the total volume of water, preferably 15 mg / L or less, more preferably 12 mg / L or less, and even more preferably 10 mg / L or less. The lower limit of the concentration of dissolved oxygen in water may be, for example, 8.0 mg / L.

[0157] The concentration of dissolved oxygen in water may be measured, for example, using a pH meter manufactured by Horiba, Ltd. (LAQUAact, a portable pH meter / water quality meter).

[0158] The temperature of the water is not particularly limited. From the viewpoint of preventing solidification and evaporation of the water and corrosion of the metal material, the temperature of the water is, for example, preferably 0 to 80°C, more preferably 2 to 75°C, and further preferably 5 to 70°C.

[0159] According to the above-mentioned method for producing a nanocrystalline film using SPSC, a nanocrystalline film having a desired pattern can be easily formed compared to conventional methods. In other words, the process for forming a nanocrystalline film using SPSC does not require a heating step or a vacuum process, and the nanocrystalline film can be formed at room temperature and atmospheric pressure. Furthermore, the process for forming a nanocrystalline film using SPSC does not require a high-temperature process such as a hydrothermal synthesis reaction, and a nanocrystalline film can be formed without using strongly alkaline water. From the above, the method for producing a nanocrystalline film using SPSC reduces the cost of the process for forming a nanocrystalline film and further reduces the environmental load associated with the process.

[0160] (Applications of nanocrystalline films) The nanocrystalline film may be used as a wiring pattern, film, layer, or quantum dot in an electronic circuit or electronic device. For example, the nanocrystalline film may be a transparent conductive film used in a touch panel, display, solar cell, or the like. The nanocrystalline film may be a semiconductor used in a thin film transistor, sensor, varistor, or the like. The nanocrystalline film may be an insulator used in an electronic device such as a capacitor. The nanocrystalline film may be a superconducting film used in a superconducting device or wire, or the like. The nanocrystalline film may be a piezoelectric material used in a SAW filter, sensor, or the like. The nanocrystalline film may be a photocatalyst used for photovoltaic power generation, air purification, or surface protection. The nanocrystalline film may be an anti-reflective film used in optical components, glasses, or UV protection glasses, or the like. The nanocrystalline film may be a surface treatment film used for surface protection.

[0161] Although the preferred embodiment of the present invention has been described above, the present invention is not necessarily limited to the above-mentioned embodiment. Various modifications of the present invention are possible without departing from the spirit of the present invention, and these modifications are also included in the present invention.

[0162] For example, by irradiating only a predetermined portion of the surface of a metal member (e.g., a first member) with concentrated light (a spot of light), a nanocrystal film having a predetermined pattern may be formed only at the portion irradiated with light. In the third embodiment, metal member 120 may have a second member containing a second metal instead of substrate 26, the first member and the second member may be electrically connected, and the second member may be molded so that the entire surface of the second member has the predetermined pattern, and the pattern of the nanocrystal film containing the first metal may be formed on the entire surface of the second member by irradiating the metal member with light. EXAMPLES

[0163] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples.

[0164] < reference Example 1> reference In Example 1, a metal member was prepared and a light irradiation step was carried out by the method described below.

[0165] (Metal parts) Zinc with a purity of 99.8% by mass was rolled to form a plate-shaped first member. The standard electrode potential of zinc (first metal) is -0.76 V. The dimensions of the first member were 50 mm x 10 mm x 0.5 mm. Next, a second member (strip-shaped pattern) made of a thin film of platinum was formed on the surface of the first member by a vacuum deposition method. By the above method, a plate-shaped first member and a second member arranged on the surface of the first member were formed. reference A metal member was obtained as in Example 1. The standard electrode potential of platinum (second metal) is 1.19 V. When depositing a thin film of platinum, a stencil mask was used and the dimensions of the deposition pattern were adjusted to 40 mm×2 mm.

[0166] (Light irradiation process) Next, a light irradiation step was carried out by the method described below. Pure water was placed in a glass container, and the metal member was immersed in the pure water. The pH and electrical conductivity of the pure water were measured with a pH meter. As the pH meter, a LAQUAact (portable pH meter / water quality meter) manufactured by Horiba, Ltd. was used. The pH of the pure water was 7.0, and the electrical conductivity of the pure water was 1.0 μS / cm or less. The container was covered with a plastic lid to seal the container.

[0167] As shown in FIG. 2, the metal member, the container, and the light source were arranged, and the surface of the metal member in the water was irradiated with light. That is, the surface of the metal member was irradiated with light from a direction perpendicular to the surface of the metal member. A xenon lamp was used as the light source. A spot light source (LightningCureLC8) manufactured by Hamamatsu Photonics K.K. was used as the xenon lamp. A dedicated optical filter was attached to the xenon lamp to set the wavelength range of the light to 400 to 600 nm. The surface of the metal member was irradiated with light for 48 hours. The light output was 280 W. The light spectrum was measured with a spectroradiometer. SOLO 2 manufactured by Gentec-EO was used as the spectroradiometer. As a result, in the spectrum of the light emitted from the xenon lamp, the wavelength with the maximum intensity was 360 nm or more and less than 620 nm. In the spectrum of the light emitted from the xenon lamp, the wavelength with the maximum intensity was about 493 nm. The light intensity at the light irradiation position 5 cm away from the light source was 3025 Wm -2 The light irradiation position may be rephrased as the position on the surface of the metal member.

[0168] < reference Example 2> reference In example 2, reference A metal member similar to that in Example 1 was prepared. Then, except for the following points, reference The light irradiation step was carried out in the same manner as in Example 1. reference In the light irradiation step of Example 2, the light irradiation time was 72 hours.

[0169] < reference Example 3> reference In example 3, reference A metal member similar to that in Example 2 was prepared. Then, except for the following points, reference The light irradiation step was carried out in the same manner as in Example 2.

[0170] referenceIn the light irradiation step of Example 3, the surface of the metal member was irradiated with simulated sunlight without using a xenon lamp as the light source. A solar simulator (HAL-320) manufactured by Asahi Spectroscopy Co., Ltd. was used as the light source of the simulated sunlight. The solar simulator used a xenon lamp. The wavelength range of the simulated sunlight emitted by the solar simulator was 350 to 1100 nm. In addition, as shown in FIG. 2, the metal member, the container, and the light source were arranged. That is, the surface of the metal member was irradiated with light from a direction perpendicular to the surface of the metal member. The light output was 300 W. The light spectrum was measured with the above-mentioned spectroradiometer. As a result, in the spectrum of the simulated sunlight, the wavelength at which the intensity was maximum was 360 nm or more and less than 620 nm. In the spectrum of the simulated sunlight, the wavelength at which the intensity was maximum was about 460 nm. The light intensity at the light irradiation position 60 cm away from the light source was 1000 W / m 2 It was.

[0171] < reference Example 4> reference In Example 4, reference A metal member similar to that in Example 2 was prepared. Then, except for the following points, reference The light irradiation step was carried out in the same manner as in Example 2.

[0172] reference In the light irradiation step of Example 4, a UV lamp was used as the light source, instead of a xenon lamp. The UV lamp used was B-100AP manufactured by UVP. The surface of the metal material was irradiated with light for 72 hours. The light output was 100 W. The light spectrum was measured with the above-mentioned spectroradiometer. As a result, in the spectrum of light emitted from the UV lamp, the wavelength with the maximum intensity was 360 nm or more and less than 620 nm. In the spectrum of light emitted from the UV lamp, the wavelength with the maximum intensity was approximately 365 nm. The light intensity at the light irradiation position 20 cm away from the light source was 100 W / m 2 It was.

[0173] < reference Example 5> reference In Example 5, referenceA metal member similar to that in Example 2 was prepared. Then, except for the following points, reference The light irradiation step was carried out in the same manner as in Example 2.

[0174] reference In the light irradiation step of Example 5, river water was used instead of pure water. The pH and electrical conductivity of the river water were measured with the pH meter. As a result, the pH of the river water was 7.5, and the electrical conductivity of the river water was 350 μS / cm.

[0175] < reference Example 6> reference In Example 6, reference A metal member similar to that in Example 2 was prepared. Then, except for the following points, reference The light irradiation step was carried out in the same manner as in Example 2.

[0176] reference In the light irradiation step of Example 6, seawater was used instead of pure water. The pH and electrical conductivity of the seawater were measured with the pH meter. As a result, the pH of the seawater was 8.2, and the electrical conductivity of the seawater was 55000 μS / cm.

[0177] < reference Example 7> reference In Example 7, the following metal members were prepared. reference The light irradiation step was carried out in the same manner as in Example 3.

[0178] (Metal parts) Zinc with a purity of 99.8% by mass was rolled to form a plate-shaped first member. The standard electrode potential of zinc (first metal) was -0.76 V. The dimensions of the first member were 50 mm x 10 mm x 0.5 mm. Next, a second member (strip-shaped pattern) made of a thin copper film was formed on the surface of the first member by a vacuum deposition method. The standard electrode potential of copper (second metal) was 0.52 V. When depositing the thin copper film, a stencil mask was used, and the dimensions of the deposition pattern were adjusted to 40 mm x 2 mm.

[0179] <Comparative Example 1> In Comparative Example 1, reference A metal member similar to that in Example 1 was prepared. Next, pure water was placed in a glass container, and the metal member was immersed in the pure water. The pH and electrical conductivity of the pure water were measured with the pH meter. As a result, the pH of the pure water was 7.0, and the electrical conductivity of the pure water was 1.0 μS / cm or less. The container was covered with a plastic lid, sealed, and held for 48 hours. In Comparative Example 1, the light irradiation process was not performed.

[0180] <Comparative Example 2> In Comparative Example 2, reference A metal member similar to that in Example 3 was prepared. Then, except for the following points, reference The light irradiation step was carried out in the same manner as in Example 3.

[0181] Acetone was used instead of pure water in the light irradiation step of Comparative Example 2. As the acetone, acetone (purity 99.5%) manufactured by Wako Pure Chemical Industries, Ltd. was used.

[0182] <Comparative Example 3> In Comparative Example 3, the following metal members were prepared. reference The light irradiation step was carried out in the same manner as in Example 3.

[0183] (Metal parts) Magnesium with a purity of 99.5% by mass was rolled to form a plate-shaped first member. The standard electrode potential of magnesium (first metal) was -2.36 V. The dimensions of the first member were 50 mm x 10 mm x 0.5 mm. Next, a second member (strip-shaped pattern) made of a thin film of platinum was formed on the surface of the first member by a vacuum deposition method. The standard electrode potential of platinum (second metal) was 1.19 V. When depositing the thin film of platinum, a stencil mask was used to adjust the dimensions of the deposition pattern to 40 mm x 2 mm.

[0184] reference The first member, second member, water, and light irradiation conditions for each of Examples 1 to 7 and Comparative Examples 1 to 3 are shown in Table 3.

[0185] [Table 3]

[0186] < reference Example 8> reference In Example 8, a metal member was prepared by the following method. reference The light irradiation step was carried out in the same manner as in Example 2.

[0187] (Metal parts) A grid mesh (pattern structure) made of copper (purity 99.9%) was used as the metal member. This grid mesh is usually used as a sample stage for a transmission electron microscope. The standard electrode potential of copper (first metal) is 0.52 V. The grid mesh had a mesh (lattice) pattern as shown in a of FIG. 5. The number of meshes in the grid mesh was 300. The dimensions of the opening of the grid mesh were 45 μm × 45 μm, and the width of the copper wires constituting the grid mesh was 38 μm.

[0188] < reference Example 9> reference In Example 9, reference A metal member similar to that in Example 8 was prepared. reference The light irradiation step was carried out in the same manner as in Example 3.

[0189] < reference Example 10> reference In Example 10, reference A metal member similar to that in Example 8 was prepared. reference The light irradiation step was carried out in the same manner as in Example 4.

[0190] < reference Example 11> reference In Example 11, the following metal members were prepared. reference The light irradiation step was carried out in the same manner as in Example 8.

[0191] (Metal parts) A grid mesh (pattern structure) made of nickel (purity 99.9%) was used as the metal member. This grid mesh is usually used as a sample stage for a transmission electron microscope. The standard electrode potential of nickel (first metal) is -0.26 V. The grid mesh had a mesh (lattice) pattern as shown in (a) of FIG. 5. The number of meshes in the grid mesh was 300. The opening dimensions of the grid mesh were 45 μm × 45 μm, and the width of the nickel wires constituting the grid mesh was 38 μm.

[0192] < reference Example 12> reference In Example 12, the following metal members were prepared. reference The light irradiation step was carried out in the same manner as in Example 8.

[0193] (Metal parts) A grid mesh made of molybdenum (purity 99.9%) was used as the metal member. This grid mesh is usually used as a sample stage for a transmission electron microscope. The standard electrode potential of molybdenum (first metal) is -0.20 V. The grid mesh had a mesh (lattice) pattern as shown in (a) of FIG. 5. The number of meshes in the grid mesh was 300. The opening dimensions of the grid mesh were 45 μm × 45 μm, and the width of the molybdenum wires constituting the grid mesh was 38 μm.

[0194] < reference Example 13> reference In Example 13, the following metal members were prepared. reference The light irradiation step was carried out in the same manner as in Example 6.

[0195] (Metal parts) A screen mesh made of stainless steel (SUS304) was used as the metal member. The standard electrode potential of SUS304 (first metal) is about -0.50 V. The screen mesh had a mesh (lattice) pattern as shown in a in FIG. 5. The number of meshes in the screen mesh was 250. Specifically, the size of the opening of the screen mesh was 72 μm × 72 μm, and the width of the stainless steel wire constituting the screen mesh was 30 μm.

[0196] <Comparative Example 4> In Comparative Example 4, reference A metal member similar to that of Example 8 was prepared. Next, pure water was poured into a glass container, and the metal member was immersed in the pure water. The pH and electrical conductivity of the pure water were measured with the pH meter. As a result, the pH of the pure water was 7.0, and the electrical conductivity of the pure water was 1.0 μS / cm or less. The container was covered with a plastic lid, sealed, and held for 72 hours. In Comparative Example 4, the light irradiation process was not performed.

[0197] <Comparative Example 5> In Comparative Example 5, reference A metal member similar to that of Example 8 was prepared. Then, except for the following points, reference The light irradiation step was carried out in the same manner as in Example 8.

[0198] Acetone was used instead of pure water in the light irradiation step of Comparative Example 5. As the acetone, acetone (purity 99.5%) manufactured by Wako Pure Chemical Industries, Ltd. was used.

[0199] reference The first members, water, and light irradiation conditions for each of Examples 8 to 13 and Comparative Examples 4 and 5 are shown in Table 4.

[0200] [Table 4]

[0201] < reference Example 14> referenceIn Example 14, a metal member was prepared by the following method. reference The light irradiation step was carried out in the same manner as in Example 2.

[0202] (First member) Zinc with a purity of 99.8% by mass was rolled to form a plate-shaped first member. The standard electrode potential of zinc (first metal) was −0.76 V. The dimensions of the first member were 70 mm×50 mm×0.5 mm.

[0203] (Substrate and conductive film) A conductive film (thin film) made of gold was formed on the surface of a plate-shaped substrate by vacuum deposition. A plate made of PET was used as the substrate. The thickness of the substrate was 50 μm. A stencil mask was used to deposit the thin gold film, and a thin film having the pattern shown in FIG. 8 was formed. The line width of the pattern was adjusted to 3.0 mm.

[0204] (Electrical connection) As shown in Fig. 6, one end of the copper wire was wound around the first member, and the other end of the copper wire was wound around the substrate. The fixing position of the copper wire on the substrate was adjusted so that the copper wire was in direct contact with the conductive film, thereby electrically connecting the first member and the conductive film formed on the surface of the substrate. reference This resulted in the metal member of Example 14. The copper wire had a line width of 0.5 mm and a purity of 99.9 mass %.

[0205] < reference Example 15> reference In Example 15, a metal member was prepared by the following method. reference The light irradiation step was carried out in the same manner as in Example 2.

[0206] (First member) Zinc with a purity of 99.8% by mass was rolled to form a plate-shaped first member. The standard electrode potential of zinc (first metal) was −0.76 V. The dimensions of the first member were 70 mm×50 mm×0.5 mm.

[0207] (Substrate and conductive film) A conductive film (thin film) made of indium tin oxide (ITO) was formed on the entire surface of a plate-shaped substrate by sputtering. A soda lime glass plate with a thickness of 50 μm was used as the substrate. The conductive film was then processed by photolithography into the pattern shown in FIG. 8. The line width of the pattern was adjusted to 3.0 mm.

[0208] (Electrical connection) As shown in Fig. 6, one end of the copper wire was wound around the first member, and the other end of the copper wire was wound around the substrate. The fixing position of the copper wire on the substrate was adjusted so that the copper wire was in direct contact with the conductive film, thereby electrically connecting the first member and the conductive film formed on the surface of the substrate. reference This resulted in the metal member of Example 15. The copper wire had a line width of 0.5 mm and a purity of 99.9 mass %.

[0209] < reference Example 16> reference In Example 16, reference A metal member similar to that in Example 15 was prepared. reference The light irradiation step was carried out in the same manner as in Example 3.

[0210] < reference Example 17> reference In Example 17, reference A metal member similar to that in Example 15 was prepared. reference The light irradiation step was carried out in the same manner as in Example 4.

[0211] < reference Example 18> reference In Example 18, a metal member was prepared by the following method. reference The light irradiation step was carried out in the same manner as in Example 15.

[0212] (First member) Iron with a purity of 99.8% by mass was rolled to form a plate-shaped first member. The standard electrode potential of iron (first metal) was −0.44 V. The dimensions of the first member were 70 mm×50 mm×0.5 mm.

[0213] (Substrate and conductive film) A conductive film (thin film) made of indium tin oxide (ITO) was formed on the entire surface of a plate-shaped substrate by sputtering. A soda lime glass plate with a thickness of 50 μm was used as the substrate. The conductive film was then processed by photolithography into the pattern shown in FIG. 8. The line width of the pattern was adjusted to 3.0 mm.

[0214] (Electrical connection) As shown in Fig. 6, one end of the copper wire was wound around the first member, and the other end of the copper wire was wound around the substrate. The fixing position of the copper wire on the substrate was adjusted so that the copper wire was in direct contact with the conductive film, thereby electrically connecting the first member and the conductive film formed on the surface of the substrate. reference This resulted in the metal member of Example 18. The copper wire had a line width of 0.5 mm and a purity of 99.9 mass %.

[0215] < reference Example 19> reference In Example 19, reference A metal member similar to that in Example 18 was prepared. reference The light irradiation step was carried out in the same manner as in Example 5.

[0216] <Comparative Example 6> In Comparative Example 6, reference A metal member similar to that of Example 15 was prepared. Next, pure water was poured into a glass container, and the metal member was immersed in the pure water. The pH and electrical conductivity of the pure water were measured with the pH meter. As a result, the pH of the pure water was 7.0, and the electrical conductivity of the pure water was 1.0 μS / cm or less. The container was covered with a plastic lid, sealed, and held for 72 hours. In Comparative Example 6, the light irradiation process was not performed.

[0217] <Comparative Example 7> In Comparative Example 7, reference The same first member, substrate, and conductive film as in Example 15 were prepared. Then, except for the following points, reference The light irradiation step was carried out in the same manner as in Example 17.

[0218] In the light irradiation step of Comparative Example 7, the first member was not electrically connected to the conductive film formed on the surface of the base material. In other words, the first member and the base material that were separated from each other and not connected by a copper wire were immersed in pure water.

[0219] <Comparative Example 8> In Comparative Example 8, reference A metal member similar to that of Example 15 was prepared. Then, except for the following points, reference The light irradiation step was carried out in the same manner as in Example 15.

[0220] Acetone was used instead of pure water in the light irradiation step of Comparative Example 8. As the acetone, acetone (purity 99.5%) manufactured by Wako Pure Chemical Industries, Ltd. was used.

[0221] reference The first members, substrates, conductive films, wiring materials, water, and light irradiation conditions for each of Examples 14 to 19 and Comparative Examples 6 to 8 are shown in Table 5.

[0222] [Table 5]

[0223] <Example 20> In Example 20, a metal member was prepared by the following method. reference The light irradiation step was carried out in the same manner as in Example 2.

[0224] (Metal parts) Copper with a purity of 99.5% by mass was rolled to form a plate-shaped first member. The standard electrode potential of copper (first metal) was 0.52 V. The dimensions of the first member were 50 mm×10 mm×0.5 mm.

[0225] Next, as shown in FIG. 9(a), reference The copper grid mesh used in Example 8 was laid on the surface of the first member. The grid mesh was fixed to the surface of the first member via a spacer so that the distance (spacing) between the surface of the first member and the surface of the grid mesh was 5 μm.

[0226] <Example 21> In Example 21, a metal member similar to that in Example 20 was prepared. reference The light irradiation step was carried out in the same manner as in Example 3.

[0227] <Example 22> In Example 22, a metal member similar to that in Example 20 was prepared. reference The light irradiation step was carried out in the same manner as in Example 4.

[0228] <Example 23> In Example 23, a metal member similar to that in Example 20 was prepared. reference The light irradiation step was carried out in the same manner as in Example 13.

[0229] <Example 24> In Example 23, the following metal member was prepared. Then, a light irradiation step was carried out in the same manner as in Example 20.

[0230] (Metal parts) A first member similar to that of Example 20 was prepared. A copper wire (linear mask material) was wound around the surface of the first member while being in contact with the surface. At this time, the pitch of the copper wire on the surface of the first member was adjusted to 2 mm. The copper wire had a line width of 0.1 mm and a purity of 99.9 mass %. The cross section of the copper wire was almost circular, and the copper wire was in linear contact with the surface of the first member, so that there was a gap between the copper wire and the surface of the first member through which water was present.

[0231] <Example 25> In Example 25, the following metal member was prepared. Then, a light irradiation step was carried out in the same manner as in Example 20.

[0232] (Metal parts) Iron with a purity of 99.5% by mass was rolled to form a plate-shaped first member. The standard electrode potential of iron (first metal) was −0.44 V. The dimensions of the first member were 50 mm×10 mm×0.5 mm.

[0233] Next, a copper grid mesh (mask material) was overlaid on the surface of the first member in the same manner as in Example 20. At this time, the grid mesh was fixed to the surface of the first member via a spacer so that the distance (spacing) between the surface of the first member and the surface of the grid mesh was 5 μm.

[0234] <Example 26> In Example 26, the following metal member was prepared. Then, a light irradiation step was carried out in the same manner as in Example 24.

[0235] (Metal parts) Zinc with a purity of 99.8% by mass was rolled to form a plate-shaped first member. The standard electrode potential of zinc (first metal) was −0.76 V. The dimensions of the first member were 50 mm×10 mm×0.5 mm.

[0236] Next, in the same manner as in Example 24, a copper wire (linear mask material) was wound around the surface of the first member while being in contact with it. At this time, the pitch of the copper wire on the surface of the first member was adjusted to 2 mm. The copper wire had a line width of 0.1 mm and a purity of 99.9 mass %. The cross section of the copper wire was almost circular, and the copper wire was in linear contact with the surface of the first member, so that there was a gap between the copper wire and the surface of the first member through which water was present.

[0237] <Comparative Example 9> In Comparative Example 9, the same metal member as in Example 20 was prepared. Next, pure water was poured into a glass container, and the metal member was immersed in the pure water. The pH and electrical conductivity of the pure water were measured with the pH meter. As a result, the pH of the pure water was 7.0, and the electrical conductivity of the pure water was 1.0 μS / cm or less. The container was covered with a plastic lid, sealed, and held for 72 hours. In Comparative Example 9, the light irradiation process was not performed.

[0238] <Comparative Example 10> In Comparative Example 10, a metal member was prepared similar to that in Example 20. Next, a light irradiation step was carried out in the same manner as in Example 20, except for the following points.

[0239] Acetone was used instead of pure water in the light irradiation step of Comparative Example 10. As the acetone, acetone (purity 99.5%) manufactured by Wako Pure Chemical Industries, Ltd. was used.

[0240] <Comparative Example 11> In Comparative Example 11, a first member was prepared similarly to that in Example 20. Next, a light irradiation step was carried out in the same manner as in Example 20, except for the following points.

[0241] In Comparative Example 11, no mask material was used.

[0242] <Comparative Example 12> In Comparative Example 12, a metal member was prepared similar to that in Example 20. Next, a light irradiation step was carried out in the same manner as in Example 20, except for the following points.

[0243] In the light irradiation step of Comparative Example 12, an infrared lamp was used instead of a xenon lamp. As the infrared lamp, a SICCA 250 W 240 V infrared lamp manufactured by OSRAM Co., Ltd. was used. The wavelength of the light from the infrared lamp was greater than 1000 nm. The light spectrum was measured with the above-mentioned spectroradiometer. As a result, in the light spectrum of the infrared lamp, the wavelength at which the intensity was maximum was 620 nm or more. In the light spectrum of the infrared lamp, the wavelength at which the intensity was maximum was approximately 1100 nm. The light intensity at the light irradiation position was an average of 35 W / m2 It was.

[0244] <Comparative Example 13> In Comparative Example 13, a first member and a mask material were prepared similarly to those in Example 20. Next, a light irradiation step was carried out in the same manner as in Example 20, except for the following points.

[0245] In Comparative Example 13, no distance was provided between the first member and the mask material, and the mask material was directly attached to the surface of the first member, i.e., no gap was provided between the mask material and the surface of the first member.

[0246] The first member, mask material, water, and light irradiation conditions for each of Examples 20 to 26 and Comparative Examples 9 to 13 are shown in Table 6.

[0247] [Table 6]

[0248] <Evaluation> (crystalline phase) reference Example 1~ 19. Examples 20- The surfaces of the metal members of Comparative Examples 26 and 1 to 12 after the light irradiation process were individually analyzed by X-ray diffraction (XRD) to identify the main crystal phases formed on the surfaces of the metal members. In Comparative Examples 1, 4, 6, and 9, the metal members were held in water for the above-mentioned time, and then the surfaces of the metal members were analyzed by X-ray diffraction (XRD) to identify the main crystal phases. In the XRD analysis, an X-ray diffractometer was used to irradiate the surface of each member with Cu-Kα rays. The measurement conditions for the XRD analysis were as follows. The X-ray diffractometer used was ATG-G (powder X-ray diffraction) manufactured by Rigaku Corporation. The compositions of the main crystal phases detected in each metal member and the locations where the crystal phases were detected are shown in Tables 7 to 10. Output: 50kV-300mA Scan speed: 4.0° / min Measurement mode: θ-2θ Diffraction angle: 10~60°

[0249] (Presence and shape of nanocrystals) reference Example 1~ 19. Examples 20- The surfaces of the metal members after the light irradiation process of each of Comparative Examples 26 and Comparative Examples 1 to 12 were individually observed using a scanning electron microscope to check for the presence or absence of nanocrystals. As the scanning electron microscope, JSM-7001F manufactured by JEOL Ltd. was used. In Comparative Examples 1, 4, 6, and 9, after the metal members were held in water for the above-mentioned time, the surfaces of each member were observed using the above-mentioned scanning electron microscope to check for the presence or absence of nanocrystals. In addition, when nanocrystals were formed, the shape of the nanocrystals was evaluated. Furthermore, elemental analysis of the microstructure generated on the surface of each member was performed by point analysis using an energy dispersive X-ray analyzer (EDX) attached to the above-mentioned scanning electron microscope.

[0250] reference As shown in Figs. 11 and 12, numerous rod-shaped and flower-shaped nanocrystals were observed on the surfaces of the metal members of Examples 1 to 7. In particular, a pattern of a nanocrystal film consisting of numerous nanocrystals was formed on the entire surface of the second member. On the other hand, the number of nanocrystals formed on the surface of the first member was significantly smaller than that on the surface of the second member. In other words, no nanocrystal film was formed on the surface of the first member itself. From the XRD and EDX analyses, the nanocrystals on the surface of the second member were mainly ZnO, and Zn(OH)2 was also present on a part of the surface of the second member. The nanocrystals formed on the surface of the first member were mainly ZnO and Zn(OH)2. reference In Examples 1 to 7, the first and second members were electrically connected and the difference in standard electrode potential between them was large, which is believed to have promoted the dissolution of zinc in the first member (reaction of the above reaction formula (1)) and the formation of Zn(OH)2 in the second member, followed by the generation and growth of ZnO (nanocrystals) by SPSC. The inventors believe that the reason why the amount of nanocrystals generated in the first member was small is as follows. reference In the configurations of the metal members of Examples 1 to 7, it is believed that ZnO due to SPSC is significantly formed on the surface of the first member. However, the electrons (e -) flowed into the second component side, the reactions shown in the above reaction formulas (3) or (9) to (10) became difficult to occur on the surface of the first component, and the hydroxide ions (OH - ) concentration is thought to have decreased.

[0251] A nanocrystalline film having a predetermined pattern was not formed on the surface of the metal member in each of Comparative Examples 1 and 2. In Comparative Examples 1 and 2, the hydroxide shown in Table 7 uniformly coated the surface of the first member.

[0252] In Comparative Example 3, a large amount of non-nanocrystalline Mg(OH)2 was formed on the surface of the first member, and no nanocrystals were found on the surface of the second member. In other words, no nanocrystalline film having a predetermined pattern was formed on the surface of the metal member in Comparative Example 3. The standard electrode potential of magnesium is low at -2.36 V, and it is believed that a direct reaction between magnesium and water proceeded. In addition, a small amount of MgO was thermodynamically formed on the surface of the first member.

[0253] [Table 7]

[0254] reference A large number of rod-shaped and flower-shaped nanocrystals were observed on the surfaces of the metal members (patterned structures) of Examples 8 to 13, as shown in Figs. 11 and 12. That is, reference In the cases of Examples 8 to 13, a nanocrystal film having a pattern similar to that of the pattern structure was formed on the surface of the pattern structure. From the XRD and EDX analyses, the nanocrystals on the surface of the metal members were mainly oxides of the metallic materials constituting each metal member. It is considered that the formation of hydroxides shown in the above reaction formulas (1) to (5) and the formation and growth of nanocrystals by SPSC shown in the above reaction formulas (7) and (8) occurred on the surface of each metal member.

[0255] No nanocrystals were formed on the surface of the metal members in Comparative Examples 4 and 5. In Comparative Examples 4 and 5, the copper hydroxide (Cu(OH)2) and copper oxide (Cu2O) shown in Table 8 uniformly covered the surface of the metal members.

[0256] [Table 8]

[0257] reference On the surfaces of the metal materials of Examples 14 to 19, numerous rod-shaped and flower-shaped nanocrystals were observed, as shown in FIGS. reference In all of Examples 14 to 19, the nanocrystals were formed only on the surface of the conductive film, and no nanocrystals were observed on the surface of the substrate itself on which the conductive film was not formed. reference In the cases of Examples 14 to 19, a nanocrystal film having a pattern similar to that of the conductive film was formed on the surface of the conductive film. XRD and EDX analyses revealed that the nanocrystals on the surface of the conductive film were mainly oxides of the metal material constituting the first member. reference In Examples 14 to 19, since the first member and the conductive film were electrically connected, it is considered that dissolution of the first metal in the first member (reaction of the above reaction formula (1)), formation of hydroxide on the conductive film, and subsequent generation and growth of oxide (nanocrystal) by SPSC were promoted. Note that the inventors consider the following reason why nanocrystals were not generated on the surface of the base material itself on which the conductive film was not formed. reference The volume resistivity of the substrates used in Examples 14 to 19 was high, and the substrates were almost insulators. Therefore, the electrons (e - ) does not permeate the entire substrate, and the reactions shown in the above reaction formulas (3) or (9) to (10) occur only on the conductive film, and the associated generation and growth of nanocrystals by SPSC also occurs only on the conductive film.

[0258] In each of Comparative Examples 6 to 8, no nanocrystals were formed on the surface of the substrate and conductive film.

[0259] [Table 9]

[0260] As shown in Figs. 11 and 12, numerous rod-shaped and flower-shaped nanocrystals were observed on the surface of the first member in Examples 20 to 26. The numerous nanocrystals were selectively formed in the light-irradiated areas of the surface of the first member, and were not formed in the non-irradiated areas (gap areas). The surface of the first member located in the gap areas maintained its metallic state. That is, in the cases of Examples 20 to 26, a nanocrystal film having the same pattern as that of the light-irradiated areas was formed on the surface of the light-irradiated areas. From the XRD and EDX analyses, it was found that the nanocrystals formed in the light-irradiated areas were mainly oxides of the metal material constituting the first member. In Examples 20 to 26, the first member had a region (gap area) where light was not irradiated and water was present in a part of its surface, which caused a difference in electron density or a difference in oxygen concentration in water between the light-irradiated area and the gap area, which led to the dissolution of the first metal from the gap area (the reaction of the above-mentioned reaction formula (1)) and the generation of hydroxide ions (OH - It is believed that the increased concentration of ZnO in the irradiated area promoted the formation of the hydroxide of the first metal and the subsequent generation of the first nanocrystals by SPSC.

[0261] No nanocrystals were formed on the surface of each of the metal members of Comparative Examples 9 and 10.

[0262] In Comparative Example 11, since no mask material was used, the nanocrystals shown in Table 10 were generated on the entire surface of the metal member. In other words, the nanocrystal film formed on the surface of the metal member in Comparative Example 11 was not patterned.

[0263] Nanocrystals were also not formed on the surface of the metal member of Comparative Example 12. It is believed that in Comparative Example 12, the irradiated light was infrared light, so the reaction for producing nanocrystals did not proceed.

[0264] Nanocrystals shown in Table 10 were formed on the light-irradiated portion of the surface of the metal member of Comparative Example 13. On the other hand, nanocrystals were not formed on the non-irradiated portion, but the non-irradiated portion was uniformly covered with a film consisting of hydroxide and oxide (Cu2O) shown in Table 10. In the case of Comparative Example 13, a part of the film formed on the light-irradiated portion was continuous with the film formed on the non-irradiated portion without interruption. In other words, in the case of Comparative Example 13, a pattern of a nanocrystal film independent of the film on the non-irradiated portion could not be selectively formed only on the light-irradiated portion. In Comparative Example 13, the first member and the mask material were in contact with each other, and almost no gaps were formed. For this reason, it is considered that the reaction by SPSC proceeded independently in the light-irradiated portion of Comparative Example 13 by the same mechanism as Comparative Example 11. On the other hand, in the non-irradiated area, water entered the small gap between the first member and the mask material, and it is believed that the metal ionization and hydroxide formation shown in the above reaction formulas (1) to (5) occurred, and furthermore, since the photoinduced tip growth by SPSC did not occur in the non-irradiated area, it is believed that the non-irradiated area was uniformly covered with non-nanocrystalline hydroxides and oxides. From the results of Comparative Example 13, it was found that in order to pattern a nanocrystalline film using a mask material, it is necessary to secure a certain amount of gaps (gap portions) in the non-irradiated area.

[0265] [Table 10] [Industrial Applicability]

[0266] According to the present invention, it is possible to easily form a nanocrystal film containing at least one of a metal oxide and a metal hydroxide and having a desired pattern, and this patterning method can be used to manufacture semiconductor devices, optical devices, and the like. [Explanation of symbols]

[0267] 2...water, 6a, 6b...container, 8a, 8b...container body, 10a, 10b...lid, 12...lamp (light source), 22a, 22c, 22d...first member, 22b...pattern structure, 24...second member, 25...nanocrystalline film, 25a...hydroxide film, 25b...oxide rod (nanorod), 26...substrate, 28...conductive film, 30...wiring material, 32...metal wire, 34...brazing material, 36...mask material, 90...exposed portion, 92...overlapping portion, 94...gap, 100, 110, 120, 130, 140...metal member, L...light, S1...area of ​​exposed portion, S2...area of ​​overlapping portion.

Claims

1. A light irradiation step of irradiating a surface of a metal member immersed in water with light to form a nanocrystal film having a predetermined pattern on the surface of the metal member, The nanocrystals in the nanocrystal film include at least one of an oxide and a hydroxide, the oxide is an oxide of a metal derived from the metal component, the hydroxide is a hydroxide of a metal derived from the metal component, the metal member includes a first member including a first metal, and a mask material overlapping a surface of the first member and fixed to the surface of the first member; the water is present between the first member and the mask material, The standard electrode potential of the first metal is greater than −2.00 V; an exposed portion of a surface of the first member that is not overlapped with the mask material has the predetermined pattern along the surface of the first member; In the light irradiation step, the nanocrystal film is formed on the surface of the exposed portion, the oxide contained in the nanocrystal is an oxide of the first metal; The hydroxide contained in the nanocrystal is a hydroxide of the first metal. Method for producing nanocrystalline films.

2. The metal member includes an alloy. The method for producing the nanocrystalline film of claim 1 .

3. The area of ​​the exposed portion is represented as S1, The area of ​​the overlapping portion of the surface of the first member where the mask material overlaps is represented as S2, The area ratio S2 / S1 is 1 / 200 to 1 / 2; A method for producing the nanocrystal film according to claim 1 or 2.

4. The light is sunlight or simulated sunlight. The method for producing the nanocrystal film according to any one of claims 1 to 3.

5. In the spectrum of the light, the wavelength at which the intensity is maximum is 360 nm or more and less than 620 nm. The method for producing the nanocrystal film according to any one of claims 1 to 4.

6. The water is at least one selected from the group consisting of pure water, ion-exchanged water, rainwater, tap water, river water, well water, filtered water, distilled water, reverse osmosis water, spring water, spring water, dam water, and seawater. The method for producing the nanocrystal film according to any one of claims 1 to 5.

7. The pH of the water is 5.00 to 10.

0. The method for producing the nanocrystal film according to any one of claims 1 to 6.

8. The electrical conductivity of the water is 0.05 to 1.0 μS / cm. The method for producing the nanocrystal film according to any one of claims 1 to 7.

9. The shape of the nanocrystal is at least one selected from the group consisting of needle-like, column-like, rod-like, tubular, scale-like, lump-like, flower-like, starfish-like, branch-like and convex-like shapes; The method for producing the nanocrystal film according to any one of claims 1 to 8.

10. The first metal is at least one selected from the group consisting of aluminum, titanium, manganese, vanadium, zinc, iron, nickel, tin, lead and copper; A method for producing a nanocrystal film according to any one of claims 1 and 3 to 9.

Citation Information

Patent Citations

  • Production of metallic material by color development

    JP1995109559A

  • Coating agent for forming inorganic oxide film capable of patterning and method for forming pattern

    JP1995304998A

  • Clear electrode and its manufacturing method

    JP2006196201A

  • Conductive film patterning method

    JP2007227300A

  • Patterning method of thin film formed of zinc oxide crystal

    JP2011134495A